Fiber-reinforced polyarylene sulfide copolymer composite substrate and producing method thereof

The fiber-enhanced polyphenylsulfide composite addresses the limitations of PPS by incorporating a high-molecular-weight copolymer with a high glass transition point and antioxidant, enhancing mechanical and chemical resistance for high-temperature applications.

JP2025012209APending Publication Date: 2025-01-24TORAY INDUSTRIES INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023114883
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing polyphenylsulfide (PPS) composites face issues with low glass transition points, reduced rigidity at high temperatures, and insufficient mechanical characteristics due to low molecular weight and slow crystallization, limiting their application in high-temperature environments.

Method used

A fiber-enhanced polyphenylsulfide composite material with a weight average molecular weight of 50,000 or more and a glass transition point of 95°C or higher, incorporating a polyphenylsulfide copolymer with a crystallization temperature of 165°C or more, and containing an antioxidant to enhance mechanical and chemical resistance.

Benefits of technology

The composite material exhibits high rigidity and excellent mechanical properties at elevated temperatures, enabling its use in structural applications where conventional PPS composites fail due to improved glass transition and crystallization characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025012209000001
    Figure 2025012209000001
  • Figure 2025012209000002
    Figure 2025012209000002
  • Figure 2025012209000003
    Figure 2025012209000003
Patent Text Reader

Abstract

To provide a fiber-reinforced polyarylene sulfide copolymer composite substrate containing a polyarylene sulfide copolymer that achieves both a high molecular weight and a high crystallization temperature, excellent in toughness at high temperature, further excellent in soaking property during production.SOLUTION: There is provided a fiber-reinforced polyarylene sulfide copolymer composite substrate impregnating a continuous reinforcing fiber or a reinforced fiber substrate in which discontinuous reinforcing fibers are dispersed with a polyarylene sulfide copolymer having a glass transition temperature of 95°C or more and 190°C or less. A weight average molecular weight of the polyarylene sulfide copolymer contained in the polyarylene sulfide copolymer composite substrate is 50,000 or more and 100,000 or less, and the crystallization temperature is 165°C or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fiber-reinforced polyarylene sulfide copolymer composite substrate and a method for producing the same. [Background technology]

[0002] Polyarylene sulfide (hereinafter sometimes abbreviated as PAS), typified by polyphenylene sulfide (hereinafter sometimes abbreviated as PPS), has properties suitable for engineering plastics, such as excellent heat resistance, barrier properties, moldability, chemical resistance, electrical insulation, and moist heat resistance, and is used mainly for injection molding and extrusion molding applications, as well as various electric and electronic parts, machine parts, automotive parts, films, fibers, etc. Due to its excellent properties, the applications of polyarylene sulfide have been expanding in recent years.

[0003] PPS, a typical PAS, is a crystalline polymer that generally has a glass transition point of 80-90°C and a melting point of 275-285°C, and is often used under high temperature conditions due to its excellent heat resistance. In addition, PPS dissolves only at high temperatures of 200-250°C in a very limited number of solvents, and is widely used in applications that take advantage of its excellent chemical resistance.

[0004] In various applications, in order to improve the mechanical properties while taking advantage of the excellent properties of PAS, it is common to melt-knead PAS with fillers such as glass fibers and additives to form a PAS resin composition for use. In order to achieve higher mechanical properties, a method is known in which a continuous reinforcing fiber is impregnated with PAS, the resulting pellets are injection-molded to obtain a molded product, and a method is known in which a continuous reinforcing fiber is impregnated with PAS to obtain a substrate. In addition, a method is known in which a reinforcing fiber substrate in which discontinuous reinforcing fibers are dispersed is impregnated with PAS. For example, Patent Document 1 discloses a continuous fiber composite containing a reactive functionalized polyarylene sulfide.

[0005] On the other hand, the glass transition point of PPS, a representative PAS, is generally 80 to 90°C, and even if the method for expressing high mechanical properties as described above is used, there is a problem that the rigidity is greatly reduced in an environment exposed to high temperatures above the glass transition point. Various studies have been conducted so far to improve the glass transition point of PAS. For example, Patent Documents 2 and 3 disclose polyarylene sulfide copolymers obtained by reacting polyarylene sulfide having a reactive functional group with rigid molecules. Patent Document 4 discloses a crystalline polyimide containing cumulative phenylene sulfide units in which the glass transition point is improved by linking dimer to nonamer phenylene sulfide and arylene groups with imide bonds. Patent Document 5 discloses a copolymer consisting of a polyarylene sulfide block and a polyetherimide block or a polydiorganosiloxane block.

[0006] In addition, Patent Document 6 discloses a fiber-reinforced polyarylene sulfide copolymer composite substrate impregnated with a polyarylene sulfide copolymer obtained by reacting a polyarylene sulfide having a reactive functional group with a rigid molecule. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Special Publication No. 2015-519423 [Patent Document 2] International Publication No. 2019 / 151288 [Patent Document 3] International Publication No. 2022 / 045105 [Patent Document 4] Japanese Patent Application Publication No. 62-84124 [Patent Document 5] Japanese Patent Application Publication No. 64-45433 [Patent Document 6] International Publication No. 2021 / 020334 Summary of the Invention [Problem to be solved by the invention]

[0008] The polyarylene sulfide contained in the continuous fiber-reinforced polyarylene sulfide disclosed in Patent Document 1 is a reactive functionalized polyarylene sulfide formed by reacting with a reactive functionalized disulfide compound in order to improve adhesion to fibers, and therefore has a relatively low molecular weight, and there is a problem of a large amount of gas caused by the disulfide compound. In addition, the polyarylene sulfide disclosed in the patent document is PPS, and therefore has insufficient heat resistance.

[0009] The polyarylene sulfide copolymers disclosed in Patent Documents 2 and 3 have a high glass transition point, but have insufficient crystallinity due to a low crystallization temperature or no crystallization temperature, and improvement of the crystallinity was expected. In addition, there was no description about the change in molecular weight when the polyarylene sulfide copolymer is in a molten state, or the stabilization or control of properties, which is used as a method of impregnating a reinforcing fiber substrate in which continuous reinforcing fibers or discontinuous reinforcing fibers are dispersed in the present invention.

[0010] The crystalline polyimide disclosed in Patent Document 4 has an improved glass transition point, but has a problem in that the molecular weight of the phenylene sulfide unit is small and crystallization is slow. In addition, there is no description about the change in molecular weight when in a molten state, or the stabilization or control of characteristics.

[0011] The copolymer disclosed in Patent Document 5 also has an improved glass transition point, but has a problem of slow crystallization due to the presence of polyetherimide blocks and polydiorganosiloxane blocks as block structures. In addition, there is no description of the change in molecular weight when in a molten state, or the stabilization or control of properties.

[0012] The fiber-reinforced polyarylene sulfide copolymer composite substrate disclosed in Patent Document 6 has a high glass transition point, but has insufficient crystallinity due to a low crystallization temperature or no crystallization temperature, and improvement of crystallinity was expected. In addition, there is no description regarding impregnation, but in the polyarylene sulfide copolymer disclosed in Patent Document 6, the molecular weight of the polyarylene sulfide copolymer impregnated into the substrate is substantially the same as the molecular weight before being used as the substrate, so that when a polyarylene sulfide copolymer with a higher molecular weight, i.e., a high viscosity, is impregnated, severe conditions such as high temperature and high pressure are required. A method for producing a fiber-reinforced polyarylene sulfide copolymer composite substrate with excellent impregnation efficiency has been desired.

[0013] An object of the present invention is to obtain a fiber-reinforced polyarylene sulfide copolymer composite substrate which contains a polyarylene sulfide copolymer that has both a high molecular weight and a high crystallization temperature, has excellent rigidity at high temperatures, and has excellent impregnation properties with the polyarylene sulfide copolymer during production. [Means for solving the problem]

[0014] The present invention has been made to solve at least part of the above-mentioned problems, and can be realized by providing the following contents. 1. A fiber-reinforced polyarylene sulfide copolymer composite substrate obtained by impregnating a reinforcing fiber substrate having continuous reinforcing fibers or discontinuous reinforcing fibers dispersed therein with a polyarylene sulfide copolymer (A) having a glass transition point of 95°C or more and 190°C or less, in which the polyarylene sulfide copolymer (B) contained in the polyarylene sulfide copolymer composite substrate has a weight-average molecular weight of 50,000 or more and 100,000 or less and a crystallization temperature of 165°C or more. 2. A fiber-reinforced polyarylene sulfide copolymer composite substrate as described in 1 above, which contains an antioxidant. 3. A fiber-reinforced polyarylene sulfide copolymer composite substrate according to the above item 1 or 2, wherein the polyarylene sulfide copolymer (B) contained in the fiber-reinforced polyarylene sulfide copolymer composite substrate has a melting point of 300° C. or lower. 4. A fiber-reinforced polyarylene sulfide copolymer composite substrate according to any one of 1 to 3 above, wherein the polyarylene sulfide copolymer (B) contained in the fiber-reinforced polyarylene sulfide copolymer composite substrate has arylene sulfide units having a number average molecular weight Mn of 1,000 or more and 10,000 or less. 5. A fiber-reinforced polyarylene sulfide copolymer composite substrate according to any one of 1 to 4 above, having a structure in which the arylene sulfide units of the polyarylene sulfide copolymer (B) contained in the fiber-reinforced polyarylene sulfide copolymer composite substrate and the copolymerization component are linked via an imide group. 6. A fiber-reinforced polyarylene sulfide copolymer composite substrate according to any one of 1 to 5 above, in which the polyarylene sulfide copolymer (B) contained in the fiber-reinforced polyarylene sulfide copolymer composite substrate has, as a structural unit, at least one structure selected from the following formulas (a) to (s):

[0015] [ka]

[0016] (R,R 1 , and R 2 is a substituent selected from hydrogen, an alkyl group having 1 to 12 carbon atoms, an arylene group having 6 to 24 carbon atoms, and a halogen group; R, R 1 , and R 2 may be the same or different.) 7. A fiber-reinforced polyarylene sulfide copolymer composite substrate according to any one of 1 to 6 above, in which the polyarylene sulfide copolymer (B) contained in the fiber-reinforced polyarylene sulfide copolymer composite substrate has a dispersity represented by weight average molecular weight / number average molecular weight of 5.0 or less. 8. A fiber-reinforced polyarylene sulfide copolymer composite substrate according to any one of 1 to 7 above, wherein the polyarylene sulfide copolymer (B) contained in the fiber-reinforced polyarylene sulfide copolymer composite substrate has a heat of fusion of 15 J / g or more. 9. A method for producing a polyarylene sulfide copolymer composite substrate, comprising impregnating a polyarylene sulfide copolymer (A) having a weight-average molecular weight of 70,000 or less into a reinforcing fiber substrate having continuous reinforcing fibers or a reinforcing fiber substrate having discontinuous reinforcing fibers dispersed therein, characterized in that the ratio of the weight-average molecular weight of the polyarylene sulfide copolymer (B) contained in the obtained polyarylene sulfide copolymer composite substrate to the weight-average molecular weight of the polyarylene sulfide copolymer (A) to be impregnated is more than 1 and not more than 10. 10. A method for producing a fiber-reinforced polyarylene sulfide copolymer composite substrate according to 9 above, comprising impregnating a reinforcing fiber substrate having continuous reinforcing fibers or discontinuous reinforcing fibers dispersed therein with the polyarylene sulfide copolymer (A) containing an antioxidant. 11. A method for producing a fiber-reinforced polyarylene sulfide copolymer composite substrate according to 9 or 10 above, comprising heating a polyarylene sulfide (C) containing amino groups in the range of 400 μmol / g or more and 5,000 μmol / g or less and experiencing a weight loss rate of 5 wt% or less when heated from 30°C to 320°C at a heating rate of 10°C / min, and at least one compound (D) selected from the following formulas (a') to (u') to obtain a polyarylene sulfide copolymer (A), and impregnating the polyarylene sulfide copolymer into a reinforcing fiber substrate having continuous reinforcing fibers or discontinuous reinforcing fibers dispersed therein.

[0017] [ka]

[0018] (X is two carboxyl groups bonded to adjacent carbon atoms, or an acid anhydride group derived from the two carboxyl groups; R, R 1 , and R2 is a substituent selected from hydrogen, an alkyl group having 1 to 12 carbon atoms, an arylene group having 6 to 24 carbon atoms, and a halogen group; R, R 1 , and R 2 may be the same or different. In addition, the aromatic ring of each compound may be di- or tri-substituted, and the multiple substituents X substituted on one aromatic ring may be the same or different. 12. The method for producing a fiber-reinforced polyarylene sulfide copolymer composite substrate according to the above item 11, wherein the heating is carried out in the presence of an antioxidant. 13. A method for producing a fiber-reinforced polyarylene sulfide copolymer composite substrate according to 11 or 12 above, in which, when polyarylene sulfide (C) and compound (D) are heated, the ratio of the total amount of half of the carboxyl groups and acid anhydride groups in compound (D) to the total amount of amino groups in polyarylene sulfide (C) exceeds 1.02. 14. The method for producing a fiber-reinforced polyarylene sulfide copolymer composite substrate according to any one of the above 11 to 13, wherein the heating is carried out substantially in the absence of a solvent. 15. A fiber-reinforced polyarylene sulfide copolymer composite substrate according to any one of 1 to 8 above, wherein the reinforcing fibers include carbon fibers and the reinforcing fibers comprise 20 to 70 volume %. Effect of the Invention

[0019] The present invention can provide a fiber-reinforced polyarylene sulfide copolymer composite substrate that contains a polyarylene sulfide copolymer that has both a high molecular weight and a high crystallization temperature, has excellent rigidity at high temperatures, and is excellent in impregnation of the polyarylene sulfide copolymer during production, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Hereinafter, an embodiment of the present invention will be described in detail.

[0021] [Fiber-reinforced polyarylene sulfide copolymer composite substrate] The fiber-reinforced polyarylene sulfide copolymer composite substrate of the present invention is a fiber-reinforced polyarylene sulfide copolymer composite substrate obtained by impregnating a reinforcing fiber substrate having continuous reinforcing fibers or discontinuous reinforcing fibers dispersed therein with a polyarylene sulfide copolymer (A) having a glass transition point of 95°C or more and 190°C or less, in which the polyarylene sulfide copolymer (B) contained in the fiber-reinforced polyarylene sulfide copolymer composite substrate has a weight-average molecular weight of 50,000 or more and 100,000 or less and a crystallization temperature of 165°C or more.

[0022] The fiber-reinforced polyarylene sulfide copolymer composite substrate of the present invention is manufactured using the polyarylene sulfide copolymer (A), and the obtained fiber-reinforced polyarylene sulfide copolymer composite substrate contains the polyarylene sulfide copolymer (B). Since the polyarylene sulfide copolymer (A) may change during the manufacturing process of the fiber-reinforced polyarylene sulfide copolymer composite substrate, the properties of the polyarylene sulfide copolymer (B) and the polyarylene sulfide copolymer (A) contained in the finally obtained fiber-reinforced polyarylene sulfide copolymer composite substrate may differ. Therefore, in the present invention, the polyarylene sulfide copolymer used as the raw material of the fiber-reinforced polyarylene sulfide copolymer composite substrate is defined as the polyarylene sulfide copolymer (A), and the polyarylene sulfide copolymer contained in the obtained fiber-reinforced polyarylene sulfide copolymer composite substrate is defined as the polyarylene sulfide copolymer (B).

[0023] The fiber-reinforced polyarylene sulfide copolymer composite substrate according to the embodiment of the present invention has either of the following two aspects. The first aspect is a fiber-reinforced polyarylene sulfide copolymer composite substrate obtained by impregnating continuous reinforcing fibers with the polyarylene sulfide copolymer (A) described below, and the second aspect is a fiber-reinforced polyarylene sulfide copolymer composite substrate obtained by impregnating a reinforcing fiber substrate having discontinuous reinforcing fibers dispersed therein with the polyarylene sulfide copolymer (A) described below.

[0024] In the embodiment of the present invention, the continuous reinforcing fiber in the first aspect refers to the reinforcing fiber being uninterrupted in the fiber-reinforced polyarylene sulfide copolymer composite substrate. Examples of the form and arrangement of the reinforcing fiber in the embodiment of the present invention include those aligned in one direction, woven fabric (cloth), knitted fabric, braided cord, tow, etc. Among them, it is preferable that the reinforcing fiber is aligned in one direction because the mechanical properties in a specific direction can be efficiently improved.

[0025] The reinforcing fiber substrate in which discontinuous fibers are dispersed in the second aspect refers to a mat-like substrate in which the reinforcing fibers are cut and dispersed in a fiber-reinforced polyarylene sulfide copolymer composite substrate. The reinforcing fiber substrate in the embodiment of the present invention can be obtained by any method, such as a wet method in which fibers are dispersed in a solution and then manufactured into a sheet, or a dry method using a carding device or an airlaid device. From the viewpoint of productivity, a dry method using a carding device or an airlaid device is preferred.

[0026] The number average fiber length of the discontinuous fibers in the reinforcing fiber substrate in the embodiment of the present invention is preferably 3 to 100 mm. If the number average fiber length of the discontinuous fibers is 3 mm or more, the reinforcing effect of the discontinuous fibers is sufficiently exhibited, and the mechanical strength of the obtained fiber-reinforced polyarylene sulfide copolymer composite substrate can be further improved. The number average fiber length is more preferably 5 mm or more. On the other hand, if the number average fiber length of the discontinuous fibers is 100 mm or less, the flowability during molding can be further improved. The number average fiber length of the discontinuous fibers is more preferably 50 mm or less, and further preferably 30 mm or less.

[0027] The number average fiber length of the discontinuous fibers in the fiber-reinforced polyarylene sulfide copolymer composite substrate according to the embodiment of the present invention can be determined by the following method. First, a sample of 100 mm x 100 mm is cut out from the fiber-reinforced polyarylene sulfide copolymer composite substrate, and the cut sample is heated in an electric furnace at 600°C for 1.5 hours to burn off the matrix resin. 400 discontinuous fibers are randomly sampled from the fired fiber-reinforced polyarylene sulfide copolymer composite substrate thus obtained. The fiber length of the sampled discontinuous fibers is measured in 1 mm units using a caliper, and the number average fiber length (Ln) can be calculated by the following formula. Ln=ΣLi / 400 (Li: measured fiber length (i = 1, 2, 3, 400) (unit: mm)).

[0028] The number average fiber length of the discontinuous fibers can be adjusted to the above range by cutting the fibers to a desired length during the production of the reinforcing fiber substrate. There is no particular restriction on the orientation of the discontinuous fibers in the reinforcing fiber substrate, but from the viewpoint of moldability, it is preferable that they are dispersed isotropically.

[0029] The type of reinforcing fiber in the first and second embodiments is not particularly limited, and examples include carbon fiber, metal fiber, organic fiber, and inorganic fiber. Two or more of these may be used.

[0030] Examples of carbon fibers include polyacrylonitrile (PAN)-based carbon fibers made from PAN fibers, pitch-based carbon fibers made from petroleum tar or petroleum pitch, cellulose-based carbon fibers made from viscose rayon or cellulose acetate, vapor-grown carbon fibers made from hydrocarbons, graphitized fibers of these, etc. Among these carbon fibers, PAN-based carbon fibers are preferably used because of their excellent balance between strength and elastic modulus.

[0031] Examples of metal fibers include fibers made of metals such as iron, gold, silver, copper, aluminum, brass, and stainless steel.

[0032] Examples of organic fibers include fibers made of organic materials such as aramid, polybenzoxazole (PBO), polyphenylene sulfide, polyester, polyamide, and polyethylene. Examples of aramid fibers include para-aramid fibers, which are excellent in strength and elastic modulus, and meta-aramid fibers, which are excellent in flame retardancy and long-term heat resistance. Examples of para-aramid fibers include polyparaphenylene terephthalamide fibers and copolyparaphenylene-3,4'-oxydiphenylene terephthalamide fibers, and examples of meta-aramid fibers include polymetaphenylene isophthalamide fibers. As aramid fibers, para-aramid fibers, which have a higher elastic modulus than meta-aramid fibers, are preferably used.

[0033] Examples of inorganic fibers include fibers made of inorganic materials such as glass, basalt, silicon carbide, and silicon nitride. Examples of glass fibers include E-glass fiber (for electrical use), C-glass fiber (for corrosion resistance), S-glass fiber, and T-glass fiber (high strength and high elastic modulus). Basalt fiber is a fiber made from basalt, a mineral, and has very high heat resistance. Basalt generally contains 9 to 25% by weight of FeO or FeO2, which is an iron compound, and 1 to 6% by weight of TiO or TiO2, which is a titanium compound, but it is also possible to increase the amount of these components in a molten state and make the fiber.

[0034] The fiber-reinforced polyarylene sulfide copolymer composite substrate in the first and second embodiments of the present invention is often expected to function as a reinforcing material, and therefore it is desirable for it to exhibit high mechanical properties. In order to exhibit high mechanical properties, it is preferable that the reinforcing fibers contain carbon fibers.

[0035] In the fiber-reinforced polyarylene sulfide copolymer composite substrate in the first and second embodiments of the present invention, the reinforcing fiber is usually composed of one or more reinforcing fiber bundles each formed by bundling a large number of single fibers. The total number of filaments (single fibers) of the reinforcing fiber when one or more reinforcing fiber bundles are arranged is preferably 1,000 to 2,000,000. From the viewpoint of productivity, the total number of filaments of the reinforcing fiber is more preferably 1,000 to 1,000,000, further preferably 1,000 to 600,000, and particularly preferably 1,000 to 300,000. The upper limit of the total number of filaments of the reinforcing fiber is not particularly limited as long as the productivity, dispersibility, and handleability can be maintained in good condition, taking into consideration the balance between dispersibility and handleability.

[0036] In the first and second embodiments of the present invention, one reinforcing fiber bundle is preferably formed by bundling 1,000 to 50,000 reinforcing monofilaments each having an average diameter of 5 to 10 μm.

[0037] The fiber-reinforced polyarylene sulfide copolymer composite substrate of the present invention is characterized by being impregnated with a polyarylene sulfide copolymer (A) having a glass transition point of 95°C or more and 190°C or less. Compared with a fiber-reinforced resin composition produced by melt-kneading reinforcing fibers and a thermoplastic resin, a fiber-reinforced resin composite substrate produced by impregnating a reinforcing fiber substrate with a thermoplastic resin has less fiber breakage during processing and high mechanical properties, so that it has been attempted to be used as a substitute for conventional metals in structural members in various industries such as automobiles, electrical and electronics, housing facilities, and aircraft. Polyphenylene sulfide, a representative polyarylene sulfide, is used in various industries by taking advantage of its excellent properties such as heat resistance, chemical resistance, high dimensional accuracy, and flame retardancy, but its glass transition point is about 90°C, which is lower than the boiling point of water. For this reason, it has been considered difficult to apply a fiber-reinforced resin composite substrate using polyphenylene sulfide to structural members, which are applications requiring high reliability. However, in recent years, as the study of resinification of structural members progresses, it is expected that the excellent properties of polyphenylene sulfide will be maintained while improving heat resistance. In the present invention, a highly reliable fiber-reinforced resin composite substrate can be provided by using a polyarylene sulfide copolymer that has chemical resistance similar to polyphenylene sulfide, a glass transition point of 95°C or more and 190°C or less, and excellent high-temperature rigidity.

[0038] The fiber-reinforced polyarylene sulfide copolymer composite substrate of the present invention preferably contains an antioxidant. By containing an antioxidant, it is easy to suppress the formation of crosslinked structures due to undesirable side reactions such as oxidative crosslinking structures and the formation of extremely high molecular weights during the process of producing the fiber-reinforced polyarylene sulfide copolymer composite substrate, and the crystallization temperature of the polyarylene sulfide copolymer (B) contained in the fiber-reinforced polyarylene sulfide copolymer composite substrate is high and the heat of fusion is easily large, and therefore the mechanical properties and chemical resistance of the fiber-reinforced polyarylene sulfide copolymer composite substrate tend to be excellent.

[0039] The antioxidant may be added when the polyarylene sulfide copolymer (A) is impregnated into a reinforcing fiber substrate in which continuous or discontinuous reinforcing fibers are dispersed, or may be added in advance to the polyarylene sulfide copolymer (A) by, for example, melt kneading or solvent dispersion, or may be heated in the presence of an antioxidant when the polyarylene sulfide (C) and the compound (D) are heated to obtain the polyarylene sulfide copolymer (A), or may be a combination of these. From the viewpoint of being able to easily suppress crosslinking structures due to side reactions and significant high molecular weight from earlier steps, it is more preferable to add the antioxidant in advance to the polyarylene sulfide copolymer (A) by, for example, melt kneading or solvent dispersion, and it is even more preferable to heat the polyarylene sulfide (C) and the compound (D) to obtain the polyarylene sulfide copolymer (A) in the presence of an antioxidant.

[0040] As the antioxidant, a representative example of the primary antioxidant is a phenol-based antioxidant, and a representative example of the secondary antioxidant is a phosphorus-based antioxidant or a sulfur-based antioxidant. In general, the primary antioxidant quickly reacts with the radicals of the polymer generated by the heat during melt processing to stabilize it, and the secondary antioxidant stabilizes it by decomposing the peroxide in a non-radical manner. The phenol-based antioxidant also plays a role in maintaining long-term heat resistance stability. The phosphorus-based antioxidant enhances processing stability during melting. The combined use of a phenol-based antioxidant with a phosphorus-based antioxidant or a sulfur-based antioxidant can prevent thermal oxidation deterioration and improve long-term heat resistance stability. The antioxidant may be used alone, or multiple antioxidants may be used in combination to prevent oxidation by multiple mechanisms. When used in high-temperature melt processing, a phenol-based antioxidant or a phosphorus-based antioxidant, which have high heat resistance, is preferred, and the combined use of a phenol-based antioxidant and a phosphorus-based antioxidant is more preferred.

[0041] The lower limit of the content of the antioxidant is, from the viewpoint of easily suppressing a crosslinked structure due to a side reaction or a significant increase in molecular weight, preferably 0.01 part by weight or more, more preferably 0.05 part by weight or more, even more preferably 0.1 part by weight or more, still more preferably 0.3 part by weight or more, and even more preferably 0.5 part by weight or more, as an added amount relative to 100 parts by weight of the polyarylene sulfide copolymer (A). In addition, since the polyarylene sulfide copolymer contains the structure represented by the above formulas (a) to (s) which is different from that of general polyarylene sulfides, and may also contain an amino group derived from the polyarylene sulfide (C) and a carboxyl group or an acid anhydride group derived from the compound (D), it is presumed that a crosslinked structure or high molecular weight is formed due to a side reaction having a mechanism different from that of general polyarylene sulfides. However, the antioxidant content is more effective when it is higher than the content in general polyarylene sulfides, and 0.3 parts by weight or more per 100 parts by weight of the polyarylene sulfide copolymer (A) is more effective, 0.4 parts by weight or more is even more effective, and 0.5 parts by weight or more is particularly effective.

[0042] The upper limit of the content of the antioxidant is preferably 10 parts by weight or less, more preferably 5 parts by weight or less, and even more preferably 3 parts by weight or less, based on 100 parts by weight of the polyarylene sulfide copolymer (A), from the viewpoints of suppressing the amount of gas generated due to the antioxidant and suppressing the deterioration of mechanical properties due to the inclusion of the antioxidant.

[0043] Examples of the phenol-based antioxidant include those having a phenolic hydroxy group and having an antioxidant effect. Examples of commonly available products include Irganox1010, Irganox1035, Irganox1076, Irganox1098, Irganox1135, Irganox1141, Irganox1330, Irganox1425WL, Irganox1520L, Irganox245, Irganox259, Irganox3114, and Irganox565 manufactured by BASF, and Adeka STAB AO-20, AO-30, AO-40, AO-50, AO-60, AO-80, and AO-330 manufactured by ADEKA. From the viewpoints of relatively excellent heat resistance of the phenol-based antioxidant and excellent effects of processing stability and long-term thermal stability, Irganox1010, Irganox1098, Irganox245, Irganox259, AO-60, AO-80, and AO-330 are preferred, and from the viewpoint of relatively excellent effects on polyarylene sulfide, AO-80 is more preferred.

[0044] Examples of phosphorus-based antioxidants include those having phosphorus atoms and having an antioxidant effect, and examples of commonly available products include Irgafos168 manufactured by BASF, and Adeka STAB PEP-8, PEP-36, HP-10, 2112, 1178, 1500, C, 135A, 3010, and TPP manufactured by ADEKA. From the viewpoint of relatively excellent heat resistance and excellent processing stability effect of phosphorus-based antioxidants, Irgafos168, PEP-8, PEP-36, HP-10, and 2112 are preferred, and from the viewpoint of relatively excellent effect on polyarylene sulfide, PEP-36 is more preferred.

[0045] Examples of sulfur-based antioxidants include those that have sulfur atoms and have an antioxidant effect, and examples of commonly available products include Irganox PS 800 FL and Irganox PS 802 FL manufactured by BASF, and Adeka STAB AO-412S, AO-503, and AO-26 manufactured by ADEKA. From the viewpoint of excellent retention of the sulfur-based inhibitor, AO-412S is preferred.

[0046] The impregnation state of the fiber-reinforced polyarylene sulfide copolymer composite substrate can be evaluated by void observation. For void observation of the fiber-reinforced polyarylene sulfide copolymer composite substrate, the fiber-reinforced polyarylene sulfide copolymer composite substrate is cut, and the thickness direction cross section of the fiber-reinforced polyarylene sulfide copolymer composite substrate is observed as follows. A sample in which the fiber-reinforced polyarylene sulfide copolymer composite substrate is embedded in epoxy resin is prepared, and the sample is polished until the thickness direction cross section of the fiber-reinforced thermoplastic resin filament can be well observed. A digital microscope (Keyence VHX-7000) microscope (CCD) is used to take a picture at a magnification of 400 times. The area ratio of the normal part and the void (air gap part) of the photographed cross section can be measured to calculate the void ratio of the fiber-reinforced polyarylene sulfide copolymer composite substrate. The void ratio is preferably 10% or less, more preferably 3% or less. When the void fraction is within this range, the mechanical properties of the fiber-reinforced polyarylene sulfide copolymer composite substrate tend to be excellent.

[0047] [Polyarylene sulfide copolymer (B) contained in fiber-reinforced polyarylene sulfide copolymer composite substrate] The glass transition point of the polyarylene sulfide copolymer (B) is substantially the same as that of the polyarylene sulfide copolymer (A) impregnated into a reinforcing fiber substrate in which continuous reinforcing fibers or discontinuous reinforcing fibers are dispersed, but may change due to the increased molecular weight depending on the heating conditions during impregnation. The lower limit of the glass transition point is preferably 95°C or higher, more preferably 100°C or higher, and even more preferably 110°C or higher. When the lower limit of the glass transition point is within this range, high rigidity can be obtained under high temperature conditions. The upper limit of the glass transition point is preferably 190°C or lower, more preferably 180°C or lower, and even more preferably 160°C or lower. When the upper limit of the glass transition point is within this range, the chemical resistance of the polyarylene sulfide copolymer composite substrate is increased. The glass transition point is defined as the inflection point of the baseline shift detected when the temperature is raised from 0°C to 340°C at a rate of 20°C / min using a differential scanning calorimeter. In order to detect the glass transition point, it is necessary to use a fiber-reinforced polyarylene sulfide copolymer composite substrate obtained by quenching from a molten state.

[0048] The crystallization temperature of the polyarylene sulfide copolymer (B) is 165°C or higher, preferably 170°C or higher, more preferably 180°C or higher, even more preferably 190°C or higher, and even more preferably 200°C or higher. If the crystallization temperature is less than 165°C, the crystallization rate is insufficient when melt-molding the fiber-reinforced polyarylene sulfide copolymer composite substrate, resulting in a decrease in productivity, and the crystallization of the resulting molded body is insufficient, resulting in a decrease in mechanical properties and chemical resistance. There is no particular limit to the upper limit of the crystallization temperature, but generally, a range of 235°C or lower can be exemplified. The crystallization temperature is the value of the crystallization peak temperature detected when the temperature is raised from 0°C to 340°C at a rate of 20°C / min using a differential scanning calorimeter, then held at 340°C for 1 minute, and cooled to 100°C at a rate of 20°C / min.

[0049] The polyarylene sulfide copolymer (B) preferably has a melting point of 300°C or less. The melting point of 300°C or less facilitates melt molding of the polyarylene sulfide copolymer composite substrate. The melting point is the melting peak temperature detected when the temperature is raised from 0°C to 340°C at a rate of 20°C / min using a differential scanning calorimeter, then held at 340°C for 1 minute, cooled to 100°C at a rate of 20°C / min, held at 100°C for 1 minute, and then raised to 340°C at a rate of 20°C / min again. The melting point can be adjusted by selecting the molecular weight of the arylene sulfide unit in the polyarylene sulfide copolymer (B). The arylene sulfide unit will be described later.

[0050] The heat of fusion of the polyarylene sulfide copolymer (B) is preferably 15 J / g or more, more preferably 20 J / g or more, and even more preferably 25 J / g or more. When the lower limit of the heat of fusion is within this range, the crystallinity of the polyarylene sulfide copolymer (B) is high, and the mechanical properties and chemical resistance of the fiber-reinforced polyarylene sulfide copolymer composite substrate tend to be excellent. There is no particular limit to the upper limit of the heat of fusion, but a range of 70 J / g or less can be generally exemplified. The heat of fusion can be calculated from the melting peak detected when a differential scanning calorimeter is used to raise the temperature from 0°C to 340°C at a rate of 20°C / min, hold at 340°C for 1 minute, lower the temperature to 100°C at a rate of 20°C / min, hold at 100°C for 1 minute, and then raise the temperature again to 340°C at a rate of 20°C / min. The heat of fusion is calculated as the heat per weight of polyarylene sulfide copolymer (B) excluding continuous reinforcing fibers in the fiber-reinforced polyarylene sulfide copolymer composite substrate or a reinforcing fiber substrate in which discontinuous reinforcing fibers are dispersed.

[0051] The lower limit of the weight-average molecular weight of the polyarylene sulfide copolymer (B) is 50,000 or more, preferably 60,000 or more. If the weight-average molecular weight is less than 50,000, the fiber-reinforced polyarylene sulfide copolymer composite substrate cannot obtain sufficient mechanical properties. The upper limit of the weight-average molecular weight is 100,000 or less. If the weight-average molecular weight exceeds 100,000, the fluidity is low and sufficient molding processability cannot be obtained when melt-molding the fiber-reinforced polyarylene sulfide copolymer composite substrate. The weight-average molecular weight of the polyarylene sulfide copolymer (B) is preferably higher than the weight-average molecular weight of the polyarylene sulfide copolymer (A) to be impregnated into the reinforcing fiber substrate in which continuous reinforcing fibers or discontinuous reinforcing fibers are dispersed. The lower limit of the ratio of the weight average molecular weight of the polyarylene sulfide copolymer (B) to the weight average molecular weight of the polyarylene sulfide copolymer (A) is preferably more than 1, more preferably 1.1 or more, even more preferably 1.2 or more, and even more preferably 1.3 or more. When the lower limit of the weight average molecular weight ratio is within this range, the impregnation state of the fiber-reinforced polyarylene sulfide copolymer composite substrate tends to be good by impregnating the polyarylene sulfide copolymer (A) with a relatively low viscosity, and the mechanical properties tend to be excellent. The upper limit of the weight average molecular weight ratio is preferably 10 or less, more preferably 8 or less, even more preferably 6 or less, and even more preferably 4 or less. When the upper limit of the ratio of the weight average molecular weight is within this range, when the polyarylene sulfide copolymer (A) is impregnated into a reinforcing fiber substrate in which continuous reinforcing fibers or discontinuous reinforcing fibers are dispersed to obtain a fiber-reinforced polyarylene sulfide copolymer composite substrate, the properties of the polyarylene sulfide copolymer (B) and the properties of the fiber-reinforced polyarylene sulfide copolymer composite substrate associated therewith tend to be more easily controlled in a stable manner. In addition, there tends to be less crosslinking structures due to undesirable side reactions, such as oxidative crosslinking structures, and the mechanical properties and chemical resistance of the fiber-reinforced polyarylene sulfide copolymer composite substrate tend to be excellent, which is also preferable. The weight average molecular weight is a value calculated in terms of polystyrene by gel permeation chromatography (GPC), which is a type of size exclusion chromatography (SEC).

[0052] The upper limit of the dispersity represented by the weight average molecular weight / number average molecular weight of the polyarylene sulfide copolymer (B) is preferably 5.0 or less, more preferably 4.0 or less. When the upper limit of the dispersity is within this range, the amount of low molecular weight components contained in the polyarylene sulfide copolymer (B) and the crosslinking structure due to undesirable side reactions such as oxidative crosslinking structures tend to be small, the mechanical properties and chemical resistance of the fiber-reinforced polyarylene sulfide copolymer composite substrate are excellent, and the amount of gas generated during melt molding of the fiber-reinforced polyarylene sulfide copolymer composite substrate also tends to be small. The lower limit of the dispersity is theoretically 1.0, which means that the polyarylene sulfide copolymer (B) has a single molecular weight, but is usually 2.0 or more. The weight average molecular weight and number average molecular weight can be determined, for example, using SEC (size exclusion chromatography) equipped with a differential refractive index detector.

[0053] The polyarylene sulfide copolymer (A) and the polyarylene sulfide copolymer (B) have substantially the same structure, and the structure of the polyarylene sulfide copolymer (B) will be described below.

[0054] The polyarylene sulfide copolymer (B) is a copolymer containing 70 mol % or more, preferably 80 mol % or more, of repeating units of the formula -(Ar-S)- as arylene sulfide units. Ar may be units represented by the following formulae (I) to (XI), among which the unit represented by formula (I) is particularly preferred.

[0055] [ka]

[0056] (R 3 ,R 4 is a substituent selected from hydrogen, an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, an aryl group having 6 to 24 carbon atoms, a halogen group, and a reactive functional group; R 3 and R 4 may be the same or different.)

[0057] As long as this repeating unit is the main constituent unit, it may contain a small amount of branching units or crosslinking units represented by the following formulas (XII) to (XIV), etc. The copolymerization amount of these branching units or crosslinking units is preferably in the range of 0 to 1 mol % per 1 mol of -(Ar-S)- units.

[0058] [ka]

[0059] (Here, Ar is a unit represented by the above formula (I) to formula (XI).)

[0060] The arylene sulfide unit may be any of a random copolymer, a block copolymer and a mixture thereof containing the above repeating unit.

[0061] Representative examples of these include polyphenylene sulfide, polyphenylene sulfide sulfone, polyphenylene sulfide ketone, random copolymers thereof, block copolymers thereof, and mixtures thereof. Particularly preferred polyarylene sulfides include p-phenylene sulfide units represented by the following formula (XV) as the main structural unit of the polymer.

[0062] [ka]

[0063] % or more, particularly 90 mol % or more of the above.

[0064] The lower limit of the number average molecular weight of the arylene sulfide unit is preferably 1,000 or more, more preferably 1,500 or more, and even more preferably 2,000 or more. When the lower limit of the number average molecular weight of the arylene sulfide unit is within this range, the chemical resistance of the polyarylene sulfide copolymer (B) tends to be high. The upper limit of the number average molecular weight of the arylene sulfide unit is preferably 10,000 or less, more preferably 6,000 or less, and even more preferably 4,000 or less. When the upper limit of the number average molecular weight of the arylene sulfide unit is 10,000 or less, the heat resistance of the polyarylene sulfide copolymer (B) tends to be high. The number average molecular weight of the arylene sulfide unit in the polyarylene sulfide copolymer (B) can be determined, for example, by treating the polyarylene sulfide copolymer (B) in a 10% aqueous sodium hydroxide solution under reflux conditions for 5 hours and then measuring the molecular weight of the residue. In order to set the number average molecular weight of the arylene sulfide unit in the polyarylene sulfide copolymer (B) within the above range, it is preferable to use a polyarylene sulfide (C) having a number average molecular weight Mn of 1,000 or more and 10,000 or less, as described below, in the production of the polyarylene sulfide copolymer (A). The weight average molecular weight and number average molecular weight can be determined, for example, by using SEC (size exclusion chromatography) equipped with a differential refractive index detector.

[0065] The structure contained in the polyarylene sulfide copolymer (B) as a copolymerization component is exemplified by a structure containing an aromatic ring, preferably the structure represented by the above formulas (a) to (s), more preferably the structure represented by the above formulas (a) to (e), (i) and (j), and among them, the structure represented by the above formula (i) is particularly preferred. By containing these structures, the crystallinity of the obtained polyarylene sulfide copolymer (B) tends to be excellent.

[0066] In the polyarylene sulfide copolymer (B), the arylene sulfide unit consisting of a repeating unit of -(Ar-S)- and the copolymerization component are preferably linked by an imide group. Linking by an imide group results in high rigidity at high temperatures. The lower limit of the imide group amount is preferably 1 mol% or more, more preferably 2 mol% or more, and even more preferably 4 mol% or more, based on the sulfur atoms in the polyarylene sulfide copolymer (B). By setting the amount in the above range, there is a tendency that the decrease in rigidity under high temperature conditions can be sufficiently suppressed. The upper limit of the imide group amount is preferably 60 mol% or less, more preferably 40 mol% or less, even more preferably 30 mol% or less, and even more preferably 20 mol% or less. If the amount of imide groups is large, the chemical resistance of the obtained polyarylene sulfide copolymer (B) tends to decrease, but by setting the amount in the above range, there is a tendency that the polyarylene sulfide copolymer (B) that exhibits sufficient chemical resistance and mechanical properties can be obtained. The amount of imide groups in the polyarylene sulfide copolymer (B) can be determined, for example, by immersing a fiber-reinforced polyarylene sulfide copolymer composite substrate in 1-chloronaphthalene at 250°C, shaking for 5 minutes, filtering through a membrane filter having a pore size of 1 μm, and cooling the filtrate to precipitate the polyarylene sulfide copolymer (B), and then washing and removing the 1-chloronaphthalene, using the FT-IR spectrum or NMR spectrum of the sample.

[0067] [Polyarylene sulfide copolymer (A) to be impregnated into a reinforcing fiber substrate having continuous reinforcing fibers or discontinuous reinforcing fibers dispersed therein] The structures of polyarylene sulfide copolymer (A) and polyarylene sulfide copolymer (B) are substantially the same, but here we will explain the characteristics of polyarylene sulfide copolymer (A) that are different from polyarylene sulfide copolymer (B).

[0068] The lower limit of the glass transition point of the polyarylene sulfide copolymer (A) is 95°C or higher, preferably 100°C or higher, and more preferably 110°C or higher. If the glass transition point is less than 95°C, high rigidity cannot be obtained under high temperature conditions. The upper limit of the glass transition point is 190°C or lower, preferably 180°C or lower, and more preferably 160°C or lower. If the glass transition point exceeds 190°C, the chemical resistance of the molded product is insufficient. The glass transition point is defined as the inflection point of the baseline shift detected when the temperature is raised from 0°C to 340°C at a rate of 20°C / min using a differential scanning calorimeter.

[0069] The lower limit of the weight average molecular weight of the polyarylene sulfide copolymer (A) is preferably 10,000 or more, more preferably 20,000 or more, even more preferably 30,000 or more, and even more preferably 40,000 or more. When the lower limit of the weight average molecular weight is within this range, the weight average molecular weight of the polyarylene sulfide copolymer (B) becomes relatively high, and the mechanical properties of the fiber-reinforced polyarylene sulfide copolymer composite substrate tend to be excellent. The upper limit of the weight average molecular weight can be exemplified as less than 100,000, and preferably 70,000 or less. When the upper limit of the weight average molecular weight is within this range, the viscosity of the polyarylene sulfide copolymer (A) is relatively low, the impregnation state of the fiber-reinforced polyarylene sulfide copolymer composite substrate tends to be good, and the mechanical properties tend to be excellent. The weight average molecular weight can be determined, for example, using SEC (size exclusion chromatography) equipped with a differential refractive index detector.

[0070] The polyarylene sulfide copolymer (A) preferably contains an antioxidant. The types and examples of the antioxidant are as described above. The antioxidant may be added to the polyarylene sulfide copolymer (A) by, for example, melt kneading or solvent dispersion, or the polyarylene sulfide (C) and the compound (D) may be heated in the presence of the antioxidant when obtaining the polyarylene sulfide copolymer (A), or a combination of these may be used. From the viewpoint of easily suppressing crosslinking structures due to side reactions and significant increase in molecular weight from earlier steps, it is more preferable to heat the polyarylene sulfide (C) and the compound (D) in the presence of an antioxidant when obtaining the polyarylene sulfide copolymer (A).

[0071] When the compound is added to the polyarylene sulfide copolymer (A) by, for example, melt kneading or solvent dispersion, the amount added per 100 parts by weight of the polyarylene sulfide copolymer (A) is as described above.

[0072] [Method for producing polyarylene sulfide copolymer (A)] The polyarylene sulfide copolymer (A) of the present invention is preferably produced by a method of heating polyarylene sulfide (C) containing amino groups in the range of 400 μmol / g to 5,000 μmol / g and exhibiting a weight loss rate of 5 wt% or less when heated from 30° C. to 320° C. at a temperature increase rate of 10° C. / min, and at least one compound (D) selected from formulas (a') to (u'). The polyarylene sulfide (C) and compound (D) will be described below.

[0073] [Polyarylene sulfide (C)] The polyarylene sulfide (C) is a homopolymer or copolymer having a repeating unit of the formula -(Ar-S)- as a main structural unit. Here, "main structural unit" means that the repeating unit is contained in an amount of 70 mol% or more. Ar may be any of the units represented by the above formulae (I) to (XI), among which the unit represented by formula (I) is particularly preferred.

[0074] As long as this repeating unit is the main constituent unit, it may contain a small amount of branching units or crosslinking units represented by the above formulas (XII) to (XIV), etc. The copolymerization amount of these branching units or crosslinking units is preferably in the range of 0 to 1 mol % per 1 mol of -(Ar-S)- units.

[0075] The polyarylene sulfide (C) may be any one of a random copolymer, a block copolymer, and a mixture thereof, containing the above repeating unit.

[0076] Representative examples of these include polyphenylene sulfide, polyphenylene sulfide sulfone, polyphenylene sulfide ketone, their random copolymers, block copolymers, and mixtures thereof. Particularly preferred polyarylene sulfides include polyphenylene sulfides containing 80 mol % or more, particularly 90 mol % or more, of p-phenylene sulfide units represented by the above formula (XV) as the main structural unit of the polymer.

[0077] The polyarylene sulfide (C) contains an amino group as a functional group. The position of the amino group may be in the main chain of the polyarylene sulfide or at the end, but terminal introduction is preferred because it is easier to control the reaction with other polymers or compounds having functional groups, and is also preferred from the viewpoint of copolymerization with compound (D) as described below. In the case of terminal introduction, it is preferable that the amino group is introduced at the p-position relative to the S bonded to Ar. In addition, polyarylene sulfide having an amino group bonded to the above Ar can also be exemplified as a preferred form. The above amino group is preferably a structure derived from compound (E), and details will be described later.

[0078] The lower limit of the amount of amino groups contained in the polyarylene sulfide (C) is preferably 400 μmol / g or more, more preferably 500 μmol / g or more, and even more preferably 700 μmol / g or more. When the lower limit of the amount of amino groups is in this range, the glass transition points of the polyarylene sulfide copolymer (A) and the polyarylene sulfide copolymer (B) tend to be sufficiently high, which is preferable. In addition, the upper limit of the amount of amino groups is preferably 5,000 μmol / g or less, more preferably 4,000 μmol / g or less, and even more preferably 3,000 μmol / g or less. When the upper limit of the amount of amino groups is in this range, it is preferable because the chemical resistance of the polyarylene sulfide copolymer (A) and the polyarylene sulfide copolymer (B) can be prevented from decreasing. The amino groups in the polyarylene sulfide (C) can be detected by, for example, 1901 cm 2 derived from a benzene ring by FT-IR analysis of the polyarylene sulfide (C). -1 Absorption at 3382 cm due to amino groups -1 It can be quantified by comparing the intensity of absorption of

[0079] The number average molecular weight of the polyarylene sulfide (C) is preferably 1,000 or more, more preferably 2,000 or more. When the lower limit of the number average molecular weight is within this range, the chemical resistance of the polyarylene sulfide copolymer (A) and the polyarylene sulfide copolymer (B) is increased, and the chemical resistance of the fiber-reinforced polyarylene sulfide copolymer composite substrate is increased. The upper limit of the number average molecular weight is preferably 10,000 or less, more preferably 6,000 or less, and even more preferably 4,000 or less. When the upper limit of the number average molecular weight is within this range, the heat resistance of the polyarylene sulfide copolymer (A) and the polyarylene sulfide copolymer (B) is increased, and the heat resistance of the fiber-reinforced polyarylene sulfide copolymer composite substrate is increased. The number average molecular weight can be determined, for example, using SEC (size exclusion chromatography) equipped with a differential refractive index detector.

[0080] The polyarylene sulfide (C) has a weight loss rate of preferably 5 wt% or less, more preferably 4 wt% or less, and even more preferably 3 wt% or less when heated from 30°C to 320°C at a temperature increase rate of 10°C / min. The smaller the weight loss rate, the more preferable it is, and the lower limit can be, for example, 0.01 wt% or more. When the example of the production method of polyarylene sulfide (C) described later is used, even if a large amount of amino groups is introduced into polyarylene sulfide (C), components that easily become gas components when heated tend not to remain.

[0081] The weight loss rate can be determined by a general thermogravimetric analysis. In this analysis, a non-oxidizing atmosphere at normal pressure is usually used. A non-oxidizing atmosphere is an atmosphere in which the oxygen concentration in the gas phase in contact with the sample is 5% by volume or less, preferably 2% by volume or less, and more preferably contains substantially no oxygen. It is preferable to use an inert gas atmosphere such as nitrogen, helium, or argon. Among these, a nitrogen atmosphere is particularly preferable from the viewpoint of economy and ease of handling. Moreover, normal pressure means atmospheric pressure, that is, a pressure condition of about 101.3 kPa in absolute pressure. Moreover, in measuring the weight loss rate, the thermogravimetric analysis is performed by increasing the temperature from room temperature to any temperature of 320°C or more at a rate of 10°C / min. This temperature range is a temperature range that is frequently used when polyarylene sulfide, such as polyphenylene sulfide, is actually used or when it is melted and molded or reacted. The weight loss rate in such a practical use temperature range is an index of the amount of gas generated from polyarylene sulfide during practical use and the degree of contamination of equipment during molding and reaction. Therefore, a polyarylene sulfide having a small weight loss rate in such a temperature range can be said to be an excellent polyarylene sulfide of high quality.

[0082] In addition, when the example of the method for producing polyarylene sulfide (C) described later is used, the crystallinity of the polyarylene sulfide copolymer obtained by using the polyarylene sulfide (C) tends to be excellent, which is preferable. This is also considered to be due to the fact that when polyarylene sulfide (C) is produced by the production method described later, components that tend to become gas components when heated are less likely to remain.

[0083] The method for producing the polyarylene sulfide (C) of the present invention will be described in detail below. Although not limited to the following method, in the present invention, a method for producing a polyarylene sulfide is preferably used in which at least a dihalogenated aromatic compound, an inorganic sulfidizing agent, and a compound (E) are reacted in an organic polar solvent in the presence of an alkali metal hydroxide, and the compound (E) is present in a range of 0.04 mol to 0.5 mol per mol of the inorganic sulfidizing agent in a reaction vessel. Here, the compound (E) is a compound having at least one aromatic ring, and having an amino group and at least one functional group selected from a hydroxyl group, a salt of a hydroxyl group, a thiol group, and a salt of a thiol group on the aromatic ring. When such a production method is selected, a functional group-containing polyarylene sulfide (C) with few impurities is obtained, and the crystallization temperature of the polyarylene sulfide copolymer (A) and the polyarylene sulfide copolymer (B) produced using the functional group-containing polyarylene sulfide copolymer (C) is likely to be high.

[0084] [Inorganic sulfidizing agent] The inorganic sulfidizing agent used in the production method of the polyarylene sulfide (C) may be any agent capable of introducing a sulfide bond into a dihalogenated aromatic compound, and examples thereof include alkali metal sulfides, alkali metal hydrosulfides, and hydrogen sulfide.

[0085] Specific examples of alkali metal sulfides include lithium sulfide, sodium sulfide, potassium sulfide, rubidium sulfide, cesium sulfide, and mixtures of two or more of these. Among these, lithium sulfide and / or sodium sulfide are preferred, and sodium sulfide is more preferred. These alkali metal sulfides can be used as hydrates or aqueous mixtures, or in the form of anhydrides. The aqueous mixture refers to an aqueous solution, or a mixture of an aqueous solution and a solid component, or a mixture of water and a solid component. Generally available, inexpensive alkali metal sulfides are hydrates or aqueous mixtures, so it is preferable to use alkali metal sulfides in such forms.

[0086] Specific examples of alkali metal hydrosulfides include lithium hydrosulfide, sodium hydrosulfide, potassium hydrosulfide, rubidium hydrosulfide, cesium hydrosulfide, and mixtures of two or more of these. Among these, lithium hydrosulfide and / or sodium hydrosulfide are preferred, and sodium hydrosulfide is more preferably used.

[0087] In addition, an alkali metal sulfide prepared in a reaction system from an alkali metal hydrosulfide and an alkali metal hydroxide can also be used. In addition, an alkali metal sulfide prepared in advance by contacting an alkali metal hydrosulfide with an alkali metal hydroxide can also be used. These alkali metal hydrosulfides and alkali metal hydroxides can be used as hydrates or aqueous mixtures, or in the form of anhydrides, with the hydrates or aqueous mixtures being preferred from the viewpoints of availability and cost.

[0088] Furthermore, an alkali metal sulfide prepared in the reaction system from an alkali metal hydroxide such as lithium hydroxide or sodium hydroxide and hydrogen sulfide can also be used.Alkali metal sulfides prepared in advance by contacting an alkali metal hydroxide such as lithium hydroxide or sodium hydroxide with hydrogen sulfide can also be used.Hydrogen sulfide may be used in any form, be it a gas, liquid, or aqueous solution.

[0089] [Compound (E)] The compound (E) used in the method for producing the polyarylene sulfide (C) is a compound having at least one aromatic ring, and having an amino group and at least one functional group selected from a hydroxyl group, a salt of a hydroxyl group, a thiol group, and a salt of a thiol group on the aromatic ring. The compound (E) may be an aromatic compound having an amino group introduced as a functional group into the polyarylene sulfide, and a hydroxyl group, a salt of a hydroxyl group, a thiol group, or a salt of a thiol group that reacts with a dihalogenated aromatic compound in the polymerization reaction step described below. Specific examples of the compound include 2-aminophenol, 4-aminophenol, 3-aminophenol, 2-aminothiophenol, 4-aminothiophenol, 3-aminothiophenol, and compounds in which the hydroxyl group or the thiol group of these compounds is a salt of an alkali metal or an alkaline earth metal. From the viewpoint of reactivity, 4-aminophenol and 4-aminothiophenol can be particularly preferred. As long as the compound has the above characteristics, it is also possible to use two or more different compounds (E) in combination. When a compound having a hydroxyl group or a thiol group is used as the compound (E), it is a preferred embodiment to use an equivalent amount of an alkali metal hydroxide at the same time. When a compound having a hydroxyl group or a thiol group in the form of a salt is used as the compound (E), it is also possible to form the salt in advance before use in the production of the polyarylene sulfide (C), or to form the salt by the reaction in a reaction vessel.

[0090] The lower limit of the amount of compound (E) used is 0.04 mol or more, preferably 0.05 mol or more, more preferably 0.06 mol or more, even more preferably 0.08 mol or more, and even more preferably 0.1 mol or more, per mol of inorganic sulfidizing agent added. The amount used is preferably this value or more, since amino groups can be sufficiently introduced into the polyarylene sulfide. The upper limit of the amount of compound (E) used is 0.5 mol or less, more preferably 0.45 mol or less, and even more preferably 0.4 mol or less, per mol of inorganic sulfidizing agent added. The amount used is preferably this value or less, since it prevents the molecular weight of the polyarylene sulfide from decreasing and prevents the mechanical properties from decreasing.

[0091] The timing of adding compound (E) is not particularly specified, and compound (E) may be added at any time during the pre-processing step, at the start of polymerization, or during the polymerization reaction step described below, or may be added in multiple batches. From the viewpoint of efficiently reacting compound (E) with dihalogenated aromatic compound, however, it is more preferable to add compound (E) at the same stage as adding dihalogenated aromatic compound to the reaction vessel.

[0092] [Dihalogenated aromatic compound] Examples of the dihalogenated aromatic compounds used in the method for producing polyarylene sulfide (C) include dihalogenated benzenes such as p-dichlorobenzene, o-dichlorobenzene, m-dichlorobenzene, p-dibromobenzene, o-dibromobenzene, m-dibromobenzene, 1-bromo-4-chlorobenzene, and 1-bromo-3-chlorobenzene, and dihalogenated aromatic compounds including compounds having substituents other than halogen such as 1-methoxy-2,5-dichlorobenzene, 1-methyl-2,5-dichlorobenzene, 1,4-dimethyl-2,5-dichlorobenzene, 1,3-dimethyl-2,5-dichlorobenzene, 2,5-dichlorobenzoic acid, 3,5-dichlorobenzoic acid, 2,5-dichloroaniline, 3,5-dichloroaniline, and bis(4-chlorophenyl)sulfide. Among them, dihalogenated aromatic compounds mainly composed of p-dihalogenated benzene represented by p-dichlorobenzene are preferred. Particularly preferably, the compound contains p-dichlorobenzene at 80 to 100 mol %, and further preferably at 90 to 100 mol %. It is also possible to use a combination of two or more different dihalogenated aromatic compounds.

[0093] The lower limit of the amount of the dihalogenated aromatic compound used is not particularly limited, but the [monomer ratio] expressed by the following formula is preferably 0.8 or more, more preferably 0.9 or more, and even more preferably 0.95 or more. By setting the [monomer ratio] in the above range, the polymerization reaction system can be stabilized and side reactions can be prevented, which is preferable. In addition, the upper limit of the amount used is not particularly limited, but the [monomer ratio] is preferably 1.2 or less, more preferably 1.1 or less, and even more preferably 1.05 or less. By setting the [monomer ratio] in the above range, the amount of halogen remaining in the polyarylene sulfide can be reduced, which is preferable. In addition, in the following formula, [amount of dihalogenated aromatic compound substance], [amount of inorganic sulfidizing agent substance], and [amount of compound (E) substance] indicate the amount of each compound used when producing polyarylene sulfide. [Monomer ratio] = [Amount of dihalogenated aromatic compound] / ([Amount of inorganic sulfidizing agent] + [Amount of compound (E)])

[0094] [Organic polar solvents] As the organic polar solvent used in the method for producing polyarylene sulfide (C) of the present invention, organic amide solvents can be preferably exemplified.Specific examples include N-alkylpyrrolidones such as N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, and N-cyclohexyl-2-pyrrolidone, caprolactams such as N-methyl-ε-caprolactam, aprotic organic solvents such as 1,3-dimethyl-2-imidazolidinone, N,N-dimethylacetamide, N,N-dimethylformamide, and hexamethylphosphoric acid triamide, and mixtures thereof, which are preferably used because of their high reaction stability.Among these, N-methyl-2-pyrrolidone and 1,3-dimethyl-2-imidazolidinone are preferred, and N-methyl-2-pyrrolidone is more preferred.

[0095] The amount of the organic polar solvent used is preferably 2.0 moles or more, more preferably 2.2 moles or more, and even more preferably 2.3 moles or more, per mole of the inorganic sulfidizing agent charged. The amount used is preferably this value or more, since polyarylene sulfide can be synthesized with good yield. The amount used is preferably 6.0 moles or less, more preferably 5.0 moles or less, and even more preferably 4.0 moles or less, per mole of the inorganic sulfidizing agent charged. The amount used is preferably this value or less, since the amount of gas generated when the resulting polyarylene sulfide (C) is heated can be reduced.

[0096] [Polymerization aid] In order to obtain a polyarylene sulfide having a relatively high degree of polymerization in a short time, it is also one of the preferred embodiments to use a polymerization aid. Here, the polymerization aid means a substance that has the effect of increasing the viscosity of the obtained polyarylene sulfide. Specific examples of such polymerization aids include organic carboxylates, water, alkali metal chlorides, organic sulfonates, alkali metal sulfates, alkaline earth metal oxides, alkali metal phosphates, and alkaline earth metal phosphates. These may be used alone, or two or more of them may be used simultaneously. Among them, organic carboxylates, water, and alkali metal chlorides are preferred, and alkali metal carboxylates are preferred as organic carboxylates, and lithium chloride is preferred as alkali metal chlorides.

[0097] The above alkali metal carboxylate has the general formula R(COOM) n (wherein R is an alkyl group, a cycloalkyl group, an aryl group, an alkylaryl group, or an arylalkyl group having 1 to 20 carbon atoms; M is an alkali metal selected from lithium, sodium, potassium, rubidium, and cesium; and n is an integer of 1 to 3). The alkali metal carboxylate can also be used as a hydrate, anhydride, or an aqueous solution. Specific examples of the alkali metal carboxylate include lithium acetate, sodium acetate, potassium acetate, sodium propionate, lithium valerate, sodium benzoate, and mixtures thereof.

[0098] The alkali metal carboxylate may be synthesized by adding and reacting an organic acid with one or more compounds selected from the group consisting of alkali metal hydroxides, alkali metal carbonates, and alkali metal bicarbonates in approximately equal chemical equivalents. Among the above alkali metal carboxylates, lithium salts are highly soluble in the reaction system and have a large auxiliary effect, but are expensive. On the other hand, potassium, rubidium, and cesium salts are thought to have insufficient solubility in the reaction system, so sodium acetate, which is inexpensive and has moderate solubility in the polymerization system, is most preferably used.

[0099] When these alkali metal carboxylates are used as polymerization aids, the amount used is usually in the range of 0.01 mol to 2 mol per mol of the charged inorganic sulfidizing agent, and in terms of obtaining a higher degree of polymerization, the range of 0.1 mol to 0.6 mol is preferable, and the range of 0.2 mol to 0.5 mol is more preferable.

[0100] When water is used as a polymerization aid, the amount added is usually in the range of 0.3 mol to 15 mol per mol of the charged inorganic sulfidizing agent, and in terms of obtaining a higher degree of polymerization, the range of 0.6 mol to 10 mol is preferable, and the range of 1 mol to 5 mol is more preferable.

[0101] Of course, two or more of these polymerization aids can be used in combination. For example, when an alkali metal carboxylate and water are used in combination, a higher molecular weight can be achieved with smaller amounts of the alkali metal carboxylate and water.

[0102] There is no particular designation for the timing of addition of these polymerization aids, and they may be added at any time during the pre-step, at the start of polymerization, or during the polymerization reaction step, which will be described later, or may be added in several batches. When an alkali metal carboxylate is used as the polymerization aid, it is more preferable to add it at the start of the pre-step or at the start of polymerization simultaneously with other additives, since this is easy to add. When water is used as the polymerization aid, it is effective to add it during the polymerization reaction step after the dihalogenated aromatic compound is charged.

[0103] [Polymerization stabilizer] A polymerization stabilizer can be used to stabilize the polymerization reaction system and prevent side reactions. The polymerization stabilizer contributes to the stabilization of the polymerization reaction system and suppresses undesirable side reactions. One indicator of side reactions is the generation of thiophenol. The addition of a polymerization stabilizer can suppress the generation of thiophenol. Specific examples of polymerization stabilizers include compounds such as alkali metal hydroxides, alkali metal carbonates, alkaline earth metal hydroxides, and alkaline earth metal carbonates. Among these, alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, and lithium hydroxide are preferred. The above-mentioned alkali metal carboxylates also act as polymerization stabilizers, and therefore are included as one of the polymerization stabilizers. In addition, when an alkali metal hydrosulfide is used as an inorganic sulfidizing agent, it is particularly preferable to use an alkali metal hydroxide at the same time, as mentioned above, but an excess of an alkali metal hydroxide relative to the sulfidizing agent can also serve as a polymerization stabilizer.

[0104] These polymerization stabilizers can be used alone or in combination of two or more. The polymerization stabilizer is preferably used in a ratio of usually 0.02 mol to 0.2 mol, preferably 0.03 mol to 0.1 mol, more preferably 0.04 mol to 0.09 mol, per mol of the inorganic sulfidizing agent charged. If this ratio is too small, the stabilizing effect is insufficient, and conversely, if it is too large, it is economically disadvantageous and the polymer yield tends to decrease.

[0105] The timing of adding the polymerization stabilizer is not particularly specified, and it may be added at any time during the pre-step, at the start of polymerization, or during the polymerization reaction step described below, or may be added in multiple portions. However, it is more preferable to add it simultaneously at the start of the pre-step or at the start of polymerization, as this is easier.

[0106] Next, a preferred method for producing the polyarylene sulfide (C) of the present invention will be specifically described in order, including a pre-process, a polymerization reaction process, a recovery process, and a post-treatment process, but the method is not limited to this method.

[0107] [Pre-process] In the method for producing the polyarylene sulfide (C), the inorganic sulfidizing agent is usually used in the form of a hydrate, and it is preferable to heat the mixture containing the organic polar solvent and the inorganic sulfidizing agent and remove excess water from the system before adding the dihalogenated aromatic compound.

[0108] As described above, the inorganic sulfidizing agent may be prepared in situ in the reaction system from an alkali metal hydrosulfide and an alkali metal hydroxide, or in a tank separate from the polymerization tank. There is no particular restriction on this method, but a preferable method is to add an alkali metal hydrosulfide and an alkali metal hydroxide to an organic polar solvent in an inert gas atmosphere at room temperature to 150°C, preferably from room temperature to 100°C, and then heat the mixture to at least 150°C or higher, preferably 180°C to 260°C, under normal pressure or reduced pressure, to distill off water. At this stage, a polymerization aid may be added, or a compound (E) may be added. Toluene or the like may be added to promote the distillation of water, and the reaction may be carried out.

[0109] The amount of water in the system at the end of the previous step, i.e., before the polymerization reaction step, is preferably 0.3 mol to 10.0 mol per 1 mol of the charged sulfidizing agent. Here, the amount of water in the system is the amount of water charged into the polymerization system minus the amount of water removed from the polymerization system. The charged water may be in any form, such as water, an aqueous solution, or water of crystallization.

[0110] [Polymerization reaction process] Polyarylene sulfide (C) is produced by reacting at least an inorganic sulfidizing agent, a dihalogenated aromatic compound and compound (E) in an organic polar solvent within a temperature range of 200° C. or higher and lower than 290° C.

[0111] When starting the polymerization reaction process, the organic polar solvent, the sulfidizing agent, and the dihalogenated aromatic compound are mixed, desirably in an inert gas atmosphere, at a temperature range of room temperature to 240°C, preferably 100°C to 230°C. Compound (E) and a polymerization aid may be added at this stage. The order of charging these raw materials may be random, or they may be charged simultaneously.

[0112] The mixture is usually heated to a temperature in the range of 200° C. to less than 290° C. There are no particular limitations on the heating rate, but a rate of 0.01° C. / min to 5° C. / min is usually selected, and a range of 0.1° C. / min to 3° C. / min is more preferable.

[0113] In general, the temperature is finally raised to 250° C. to less than 290° C., and the reaction is carried out at that temperature for usually 0.25 hours to 50 hours, preferably 0.5 hours to 20 hours.

[0114] In order to obtain a higher degree of polymerization, it is effective to react at 200° C. to 260° C. for a certain period of time before the final temperature is reached, and then to raise the temperature to 270° C. to less than 290° C. In this case, the reaction time at 200° C. to 260° C. is usually selected within the range of 0.25 hours to 20 hours, and preferably 0.25 hours to 10 hours.

[0115] In order to adjust the molecular weight of the polymer, it is possible to add compound (E) during the polymerization. However, from the viewpoint of efficient reaction of compound (E), it is more preferable to add at least a part of compound (E) at the same stage as the dihalogenated aromatic compound.

[0116] [Recovery process] In the method for producing the polyarylene sulfide (C), after the polymerization is completed, a solid matter is recovered from the polymerization reaction product containing the polymer, the solvent, etc. As the recovery method, any known method may be adopted.

[0117] For example, after the polymerization reaction is completed, the polymer particles may be collected by gradually cooling. The cooling speed is not particularly limited, but is usually about 0.1°C / min to 3°C / min. It is not necessary to cool at the same speed throughout the entire cooling process, and a method of gradually cooling at a speed of 0.1°C / min to 1°C / min until the polymer particles crystallize and precipitate, and then at a speed of 1°C / min or more may be used.

[0118] Another preferred method is to carry out the above recovery under rapid cooling conditions. A preferred recovery method is the flash method. In the flash method, the polymerization reaction product is subjected to high temperature and high pressure (usually 250°C or higher, 8 kg / cm 2 This is a method in which the polymer is flashed from the above state into an atmosphere of normal pressure or reduced pressure, and the polymer is powdered and recovered while the solvent is recovered. Flashing here means that the polymerization reaction product is ejected from a nozzle. Specific examples of the flashing atmosphere include nitrogen or water vapor at normal pressure, and the temperature is usually selected in the range of 150°C to 250°C.

[0119] [Post-processing process] After the polyarylene sulfide (C) is produced through the above-mentioned polymerization reaction step and recovery step, it can be subjected to a post-treatment step of acid treatment, hot water treatment, or washing with an organic solvent. From the viewpoint of removing impurities, the post-treatment step is preferably any one of acid treatment, hot water treatment, and washing with an organic solvent, and more preferably two or more types of treatments are used in combination.

[0120] The acid treatment is carried out as follows. The acid used in the acid treatment is not particularly limited as long as it does not have the effect of decomposing the polyarylene sulfide (C), and examples thereof include acetic acid, hydrochloric acid, sulfuric acid, phosphoric acid, silicic acid, carbonic acid, and propylic acid. Among them, acetic acid and hydrochloric acid are more preferably used. On the other hand, an acid such as nitric acid that decomposes and deteriorates the polyarylene sulfide (C) is not preferred. The acid treatment method includes, for example, a method of immersing the polyarylene sulfide (C) in an acid or an aqueous solution of an acid, and stirring or heating is also possible if necessary. When an acid solution is used, the solution may be a solution using an organic solvent or an aqueous solution, but an aqueous solution is preferred from the viewpoint of the miscibility of the acid and the tendency of the solubility of the salt and basic components contained in the polyarylene sulfide to be relatively high, and the water used is preferably distilled water or deionized water in order not to impair the effect of the preferred chemical modification of the polyarylene sulfide. For example, when acetic acid is used, the polyarylene sulfide (C) powder is immersed in an aqueous acetic acid solution of pH 4 heated to 80°C to 200°C, and stirred for 30 minutes to obtain a sufficient effect. The pH after the treatment may be 4 or more, for example, about pH 4 to 8. In order to remove the acid or salt remaining in the polyarylene sulfide (C) that has been subjected to the acid treatment, it is preferable to further wash it several times with water or hot water. The water used for washing is preferably distilled water or deionized water so as not to impair the effect of the preferable chemical modification of the polyarylene sulfide (C). When the acid treatment is performed, it is preferable because when a polyarylene sulfide copolymer is obtained using the polyarylene sulfide (C), a polyarylene sulfide copolymer with a higher molecular weight tends to be obtained.

[0121] The hot water treatment is carried out as follows. When the polyarylene sulfide (C) is subjected to hot water treatment, the temperature of the hot water is preferably 100°C or higher, more preferably 120°C or higher, further preferably 150°C or higher, and particularly preferably 170°C or higher. If the temperature is less than 100°C, the effect of the preferable chemical modification of the polyarylene sulfide is small, which is not preferable. In order to realize the effect of the preferable chemical modification of the polyarylene sulfide (C) by the hot water treatment, it is preferable that the water used is distilled water or deionized water. There is no particular restriction on the operation of the hot water treatment. The hot water treatment is carried out by a method in which a predetermined amount of polyarylene sulfide (C) is added to a predetermined amount of water, and heated and stirred in a pressure vessel, or a method in which hot water treatment is carried out continuously. The ratio of polyarylene sulfide (C) to water is preferably more water, but a bath ratio (weight of cleaning solution relative to weight of dry polyarylene sulfide (C)) of 200 g or less of polyarylene sulfide (C) per 1 liter of water is usually selected. In order to avoid undesirable decomposition of the reactive functional groups at the terminals, it is preferable to carry out the treatment under an inert atmosphere. Furthermore, in order to remove remaining components, it is preferable to wash the polyarylene sulfide (C) after the hot water treatment operation several times with warm water.

[0122] The case of washing with an organic solvent is as follows. The organic solvent used for washing the polyarylene sulfide (C) is not particularly limited as long as it does not have the action of decomposing the polyarylene sulfide. For example, examples of the organic solvent used for washing the polyarylene sulfide (C) include nitrogen-containing polar solvents such as N-methyl-2-pyrrolidone, dimethylformamide, and dimethylacetamide, sulfoxide-sulfone solvents such as dimethyl sulfoxide, dimethyl sulfone, and sulfolane, ketone solvents such as acetone, methyl ethyl ketone, diethyl ketone, and acetophenone, ether solvents such as dimethyl ether, dipropyl ether, dioxane, and tetrahydrofuran, halogen-based solvents such as chloroform, methylene chloride, trichloroethylene, ethylene dichloride, and perchloroethylene, alcohol-based solvents such as methanol, ethanol, propanol, butanol, pentanol, ethylene glycol, and propylene glycol, and aromatic hydrocarbon-based solvents such as benzene, toluene, and xylene. Among these organic solvents, N-methyl-2-pyrrolidone, acetone, dimethylformamide, and chloroform are preferably used. From the viewpoint of removing impurities having an arylene sulfide structure, nitrogen-containing polar solvents that tend to provide relatively high solubility, such as N-methyl-2-pyrrolidone, dimethylformamide, and chloroform, are particularly preferred. These organic solvents may be used alone or in a mixture of two or more, or may be used mixed with water. For example, the method of washing with an organic solvent includes a method of immersing the polyarylene sulfide (C) in the organic solvent, and stirring or heating may be performed as necessary. There is no particular restriction on the washing temperature when washing the polyarylene sulfide (C) with an organic solvent, and any temperature from room temperature to about 300°C may be selected. The higher the washing temperature, the higher the washing efficiency tends to be, but usually a washing temperature of room temperature to 150°C is sufficient to obtain a sufficient effect. It is also possible to wash under pressure at a temperature equal to or higher than the boiling point of the organic solvent in a pressure vessel. There is also no particular restriction on the washing time. Although it depends on the washing conditions, in the case of batch washing, usually washing for 5 minutes or more will provide a sufficient effect. It is also possible to wash in a continuous manner.Washing with an organic solvent is preferable because it reduces the amount of gas generated when the polyarylene sulfide (C) is heated, and also because it tends to facilitate the production of a high molecular weight product when the polyarylene sulfide copolymer (A) described below is obtained using the polyarylene sulfide (C).

[0123] [Thermal oxidation crosslinking treatment] The polyarylene sulfide (C) can be used after being made to have a high molecular weight by a thermal oxidation crosslinking treatment, such as heating in an oxygen atmosphere or heating with a crosslinking agent such as peroxide added thereto, after the completion of polymerization. However, the number average molecular weight of the polyarylene sulfide (C) is preferably 10,000 or less.

[0124] [Compound (D)] The compound (D) is at least one selected from the above formulas (a') to (u').

[0125] X is selected from two carboxyl groups bonded to two adjacent carbon atoms, or an acid anhydride group derived from the two carboxyl groups. From the viewpoint of reactivity when the above-mentioned polyarylene sulfide (C) and compound (D) are heated, X is preferably an acid anhydride group derived from two carboxyl groups bonded to two adjacent carbon atoms. R, R 1 , and R 2 is a substituent selected from hydrogen, an alkyl group having 1 to 12 carbon atoms, an arylene group having 6 to 24 carbon atoms, and a halogen group; R, R 1 , and R 2 may be the same or different. Hydrogen, a methyl group, an ethyl group, or a propyl group is preferred from the viewpoint of availability. The aromatic ring of each compound may be di- or tri-substituted, and the multiple substituents X substituted on one aromatic ring may be the same or different.

[0126] Specific examples of the compound (D) include pyromellitic acid, 3,3',4,4'-thiodiphthalic acid, 3,3',4,4'-sulfonyldiphthalic acid, 3,3',4,4'-benzophenonetetracarboxylic acid, 3,3',4,4'-sulfinyldiphthalic acid, 3,3',4,4'-biphenyltetracarboxylic acid, 3,3',4,4'-tetracarboxyldiphenylmethane, 9,9-bis(3,4-dicarboxyphenyl)fluorene, naphthalene-1,4,5,8-tetracarboxylic acid, bicyclo[2.2.2]oct-7-ene- 2,3,5,6-Tetracarboxylic acid, 3,4,9,10-perylenetetracarboxylic acid, pyromellitic anhydride, 3,3',4,4'-thiodiphthalic anhydride, 3,3',4,4'-sulfonyldiphthalic anhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-sulfinyldiphthalic anhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-tetracarboxydiphenylmethane dianhydride, 9,9-bis(3,4-dicarboxyphenyl)phthalate Examples of suitable amines include fluorene dianhydride, naphthalene-1,4,5,8-tetracarboxylic dianhydride, glycerin bisanhydrotrimellitate monoacetate, ethylene glycol bisanhydrotrimellitate, bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride, 3,4,9,10-perylenetetracarboxylic dianhydride, 4,4'-thiodibenzoic acid, 4,4'-dicarboxylbenzophenone, 4,4'-sulfinyldibenzoic acid, and 4,4'-dicarboxylbiphenyl. From the viewpoint of reactivity, From these, 3,3',4,4'-thiodiphthalic anhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-sulfinyldiphthalic anhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, 4,4'-thiodibenzoic acid, 4,4'-dicarboxylbenzophenone, 4,4'-sulfinyldibenzoic acid, 4,4'-dicarboxylbiphenylpyromellitic acid, and pyromellitic anhydride are preferably used.

[0127] [Heating conditions of polyarylene sulfide (C) and compound (D)] The polyarylene sulfide copolymer can be produced by heating the polyarylene sulfide (C) and the compound (D).

[0128] When the polyarylene sulfide (C) and the compound (D) are heated, the ratio of the total amount of the amino groups of the polyarylene sulfide (C) to the half of the amount of the carboxyl groups and the acid anhydride groups of the compound (D) is preferably 0.75 or more and 1.25 or less. By making it in this range, the obtained polyarylene sulfide copolymer (A) tends to have a high molecular weight and exhibit sufficient mechanical properties and chemical resistance. The lower limit of the ratio of the total amount of the amino groups of the polyarylene sulfide (C) to the half of the amount of the carboxyl groups and the acid anhydride groups of the compound (D) is preferably 0.75 or more, more preferably 0.8 or more, even more preferably 0.9 or more, even more preferably 1.0 or more, and particularly preferably more than 1.02. Although the reason is not clear at present, when the lower limit of the ratio is within this range, the glass transition point is sufficiently high, and the polyarylene sulfide copolymer (A) tends to have excellent crystallinity, a high crystallization temperature, and excellent mechanical properties and chemical resistance.

[0129] The heating of the polyarylene sulfide (C) and the compound (D) may be performed by mixing the entire amount from the beginning and heating, or by mixing and heating at least a part of the polyarylene sulfide (C) and at least a part of the compound (D), and then mixing and heating the remaining polyarylene sulfide (C) and / or the compound (D). In the latter case, the remaining polyarylene sulfide (C) and / or the compound (D) may be mixed and heated after mixing and heating at least a part of the polyarylene sulfide (C) and at least a part of the compound (D), or the product may be taken out once, and the remaining polyarylene sulfide (C) and / or the compound (D) may be mixed and heated after mixing and heating at least a part of the polyarylene sulfide (C) and at least a part of the compound (D), and then heated. From the viewpoint of efficiently obtaining the polyarylene sulfide copolymer (A), it is preferable to mix and heat the entire amount of the polyarylene sulfide (C) and the compound (D) from the beginning. On the other hand, from the viewpoint of easily controlling and adjusting the thermal properties of the polyarylene sulfide copolymer (A), such as the glass transition point, crystallization temperature, and melting point, as well as the molecular weight, the terminal type and its amount depending on the application, it is preferable to mix and heat at least a part of the polyarylene sulfide (C) and at least a part of the compound (D), and then mix and heat the remaining polyarylene sulfide (C) and / or compound (D).

[0130] The lower limit of the heating temperature is 200°C or more, preferably 230°C or more, and more preferably 250°C or more. By setting the lower limit of the heating temperature in such a range, the reaction between the polyarylene sulfide (C) and the compound (D) can be easily promoted, and by setting the temperature to the temperature at which the polyarylene sulfide (C) melts or higher, the reaction tends to be promoted in a shorter time. The temperature at which the polyarylene sulfide (C) melts cannot be uniquely indicated because it varies depending on the composition and molecular weight of the polyarylene sulfide (C) and the environment during heating, but it can be grasped, for example, by analyzing the polyarylene sulfide (C) with a differential scanning calorimeter. The upper limit of the heating temperature is 400°C or less, preferably 380°C or less, more preferably 360°C or less. By setting the upper limit of the heating temperature within such a range, undesirable side reactions such as crosslinking reactions and decomposition reactions between polyarylene sulfides (C) can be suppressed, and deterioration of the properties of the obtained polyarylene sulfide copolymer (A) can be suppressed.

[0131] The heating time varies depending on the composition and molecular weight of the polyarylene sulfide (C) and the heating environment, so it cannot be uniquely specified, but it is preferable to set it so that the above-mentioned undesirable side reactions do not occur as much as possible. The lower limit of the heating time can be 0.1 minutes or more, preferably 1 minute or more, more preferably 2 minutes or more, and even more preferably 3 minutes or more. By setting the lower limit of the heating time in such a range, the reaction between the polyarylene sulfide (C) and the compound (D) can be more sufficiently promoted. The upper limit of the heating time can be 100 hours or less, preferably 20 hours or less, more preferably 10 hours or less, and even more preferably 1 hour or less. By setting the upper limit of the heating time in such a range, it is economical and tends to avoid the above-mentioned undesirable side reactions.

[0132] Heating can be performed in the absence of a solvent or in the presence of a solvent. When heating is performed in the presence of a solvent, the solvent is not particularly limited as long as it does not substantially cause undesirable side reactions such as decomposition or crosslinking of the produced polyarylene sulfide copolymer (A). The solvent can be used as one type or a mixture of two or more types. On the other hand, from the viewpoint of efficiently obtaining the polyarylene sulfide copolymer (A), it is preferable to perform the heating under substantially solvent-free conditions. In addition, from the viewpoint of preventing contamination and deterioration of properties due to generated gases when impregnating the obtained polyarylene sulfide copolymer (A) into a reinforcing fiber substrate in which continuous reinforcing fibers or discontinuous reinforcing fibers are dispersed, and when melt molding the fiber-reinforced polyarylene sulfide copolymer composite substrate, it is preferable to perform the heating under substantially solvent-free conditions. Here, the substantially solvent-free conditions refer to a system in which the polyarylene sulfide (C) and the compound (D) are heated, in which the solvent is 10% by weight or less, and preferably 3% by weight or less.

[0133] Heating in the production method of the polyarylene sulfide copolymer (A) of the present invention can be carried out not only by a method using a conventional polymerization reaction apparatus, but also in a mold for producing a molded product, or by using an extruder or a melt kneader, and can be carried out without any particular limitation as long as the apparatus is equipped with a heating mechanism, and known methods such as a batch method and a continuous method can be adopted.

[0134] The atmosphere during heating is preferably a non-oxidizing atmosphere, and it is also preferable to carry out the heating under reduced pressure conditions. In addition, when carrying out the heating under reduced pressure conditions, it is preferable to first change the atmosphere in the reaction system to a non-oxidizing atmosphere and then to a reduced pressure condition. This tends to suppress undesirable side reactions such as crosslinking reactions and decomposition reactions between polyarylene sulfides (C) and between the polyarylene sulfide copolymers (A) produced. The non-oxidizing atmosphere refers to an atmosphere in which the oxygen concentration in the gas phase is 5% by volume or less, preferably 2% by volume or less, and more preferably an atmosphere that does not substantially contain oxygen, that is, an inert gas atmosphere such as nitrogen, helium, or argon, and among these, a nitrogen atmosphere is particularly preferable from the standpoint of economy and ease of handling. In addition, the reduced pressure condition refers to a pressure in the reaction system that is lower than atmospheric pressure, and the upper limit of the pressure is preferably 50 kPa or less, more preferably 20 kPa or less, and even more preferably 10 kPa or less. By setting the upper limit of the pressure in such a range, undesirable side reactions such as crosslinking reactions tend to be suppressed. The lower limit of the pressure can be exemplified as 0.1 kPa or more. By setting the lower limit of the pressure to 0.1 kPa or more, it is possible to avoid a load on the reaction apparatus caused by reducing the pressure more than necessary.

[0135] The heating is preferably carried out in the presence of an antioxidant, the types and examples of which are as described above.

[0136] When the heating is carried out in the presence of an antioxidant, the lower limit of the amount of the antioxidant to be added is preferably 0.01 part by weight or more, more preferably 0.05 part by weight or more, even more preferably 0.1 part by weight or more, still more preferably 0.3 part by weight or more, and even more preferably 0.5 part by weight or more, relative to 100 parts by weight of the polyarylene sulfide (C), from the viewpoint of easily suppressing crosslinked structures and significant increase in molecular weight due to side reactions during heating and when the polyarylene sulfide copolymer (A) obtained by heating is used. In addition, it is presumed that the polyarylene sulfide copolymer (A) obtained by heating contains a structure represented by the above formulas (a) to (s) which is different from that of general polyarylene sulfides, and may also contain amino groups derived from the polyarylene sulfide (C) and carboxyl groups or acid anhydride groups derived from the compound (D), and therefore crosslinked structures and high molecular weight are formed due to side reactions having a mechanism different from that of general polyarylene sulfides. However, the antioxidant content is more effective when it is higher than the content in general polyarylene sulfides, and an addition amount of 0.3 parts by weight or more per 100 parts by weight of polyarylene sulfide (C) is more effective, 0.4 parts by weight or more is even more effective, and 0.5 parts by weight or more is particularly effective.

[0137] When heating is performed in the presence of an antioxidant, the upper limit of the amount of antioxidant added is preferably 10 parts by weight or less, more preferably 5 parts by weight or less, and even more preferably 3 parts by weight or less, per 100 parts by weight of polyarylene sulfide (C), from the viewpoints of suppressing the amount of gas generated due to the antioxidant and suppressing the deterioration of the mechanical properties of the polyarylene sulfide copolymer due to the inclusion of the antioxidant.

[0138] The relationship between the amount of antioxidant added per 100 parts by weight of polyarylene sulfide (C) and the content per 100 parts by weight of polyarylene sulfide copolymer (A) can be calculated as follows when the weight of the produced polyarylene sulfide copolymer (A) is known. [Content per 100 parts by weight of polyarylene sulfide copolymer (A)]=[Amount added per 100 parts by weight of polyarylene sulfide (C)]×[Weight of polyarylene sulfide (C)] / [Weight of produced polyarylene sulfide copolymer (A)] (The weight of the produced polyarylene sulfide copolymer (A) can theoretically be calculated by weighing the product and subtracting the weight of the added antioxidant.)

[0139] [Method for producing fiber-reinforced polyarylene sulfide copolymer composite substrate] The fiber-reinforced polyarylene sulfide copolymer composite substrate according to the embodiment of the present invention can be obtained by impregnating continuous reinforcing fibers with the polyarylene sulfide copolymer (A) (first embodiment), or by impregnating a reinforcing fiber substrate in which discontinuous reinforcing fibers are dispersed with the polyarylene sulfide copolymer (A) (second embodiment).

[0140] In the first embodiment, examples of the method for impregnating the continuous reinforcing fibers with the polyarylene sulfide copolymer (A) include a film method in which a film-shaped polyarylene sulfide copolymer (A) is melted and pressurized to impregnate the reinforcing fiber bundle with the polyarylene sulfide copolymer (A); a method in which the fibrous polyarylene sulfide copolymer (A) is mixed with a reinforcing fiber bundle, and then the fibrous polyarylene sulfide copolymer (A) is melted and pressurized to impregnate the reinforcing fiber bundle with the polyarylene sulfide copolymer (A); Examples of the method include a commingle method in which a reinforcing fiber bundle is impregnated with a polyarylene sulfide copolymer (A); a powder method in which a powdered polyarylene sulfide copolymer (A) is dispersed in the gaps between the fibers in the reinforcing fiber bundle, and then the powdered polyarylene sulfide copolymer (A) is melted and pressurized to impregnate the reinforcing fiber bundle with the polyarylene sulfide copolymer (A); and a pultrusion method in which a reinforcing fiber bundle is immersed in molten polyarylene sulfide copolymer (A) and pressurized to impregnate the reinforcing fiber bundle with the polyarylene sulfide copolymer (A). Any of these methods may be used.

[0141] The thickness of the fiber-reinforced polyarylene sulfide copolymer composite substrate in the first embodiment of the present invention is preferably 0.1 to 10 mm. If the thickness is 0.1 mm or more, the strength of a molded article obtained by using the fiber-reinforced polyarylene sulfide copolymer composite substrate can be improved. 0.2 mm or more is more preferable. On the other hand, if the thickness is 1.5 mm or less, it is easier to impregnate the reinforcing fibers with the polyarylene sulfide copolymer (A). 1 mm or less is more preferable, 0.7 mm or less is even more preferable, and 0.6 mm or less is even more preferable.

[0142] In the first embodiment of the present invention, the volume content of the reinforcing fibers in the fiber-reinforced polyarylene sulfide copolymer composite substrate is preferably 20 to 70% by volume. In other words, the fiber-reinforced polyarylene sulfide copolymer composite substrate preferably contains 20 to 70% by volume (20% by volume or more and 70% by volume or less) of the reinforcing fibers relative to the entire fiber-reinforced polyarylene sulfide copolymer composite substrate (100% by volume). By containing 20% ​​by volume or more of the reinforcing fibers, the strength of the molded product obtained by using the fiber-reinforced polyarylene sulfide copolymer composite substrate can be further improved. 30% by volume or more is more preferable, and 40% by volume or more is even more preferable. On the other hand, by containing 70% by volume or less of the reinforcing fibers, the reinforcing fibers are more easily impregnated with the polyarylene sulfide copolymer (A). 60% by volume or less is more preferable, and 55% by volume or less is even more preferable. The volume content can be adjusted to a desired range by adjusting the input amounts of the reinforcing fibers and the polyarylene sulfide copolymer (A).

[0143] The volume fraction of reinforcing fibers in fiber-reinforced polyarylene sulfide copolymer composites (V f ) can be calculated by measuring the mass W0 of the fiber-reinforced polyarylene sulfide copolymer composite substrate, immersing it in 1-chloronaphthalene at 250°C, measuring the mass W1 of the reinforcing fibers remaining as a residue after dissolving the polyarylene sulfide copolymer (B), and using the following formula. V f (Volume%) = (W1 / ρ f ) / {W1 / ρ f +(W0-W1) / ρ r}×100 ρ f : Density of reinforcing fiber (g / cm 3 ) ρ r : Density of polyarylene sulfide copolymer (g / cm 3 )

[0144] In addition, the fiber-reinforced polyarylene sulfide copolymer composite substrate according to the embodiment of the present invention can be selected according to the desired impregnation property depending on the usage and purpose. For example, prepreg with higher impregnation property, semi-preg with half impregnation property, fabric with low impregnation property, etc. are included. In general, a molding material with higher impregnation property is preferable because a molded product with excellent mechanical properties can be obtained by molding in a short time.

[0145] In the second embodiment of the present invention, examples of the method for impregnating the reinforcing fiber substrate having dispersed therein with the polyarylene sulfide copolymer (A) include a method in which the polyarylene sulfide copolymer (A) is supplied by an extruder to impregnate the reinforcing fiber substrate, a method in which the powdered polyarylene sulfide copolymer (A) is dispersed in the fiber layer of the reinforcing fiber substrate and melted to impregnate the substrate, a method in which the polyarylene sulfide copolymer (A) is made into a film and laminated with the reinforcing fiber substrate and melted to impregnate the film, a method in which the polyarylene sulfide copolymer (A) is dissolved in a solvent and impregnated into the reinforcing fiber substrate in the form of a solution, and then the solvent is volatilized, a method in which the polyarylene sulfide copolymer (A) is fiberized to form a mixed yarn with discontinuous fibers, and a method in which the polyarylene sulfide copolymer (A) is laminated using a melt-blown nonwoven fabric. Either method may be used, but the method of supplying the polyarylene sulfide copolymer (A) by an extruder and impregnating the reinforcing fiber substrate has the advantage that it is not necessary to process the polyarylene sulfide copolymer (A), the method of dispersing the powdered polyarylene sulfide copolymer (A) in the fiber layer of the reinforcing fiber substrate and melting it has the advantage that impregnation is easy, and the method of forming the polyarylene sulfide copolymer (A) into a film and laminating it with the reinforcing fiber substrate has the advantage that a relatively good quality product can be obtained.

[0146] The thickness of the fiber-reinforced polyarylene sulfide copolymer composite substrate in the second embodiment of the present invention is preferably 0.1 to 10 mm. If the thickness is 0.1 mm or more, the strength of a molded article obtained by using the fiber-reinforced polyarylene sulfide copolymer composite substrate can be improved. It is more preferably 1 mm or more. On the other hand, if the thickness is 10 mm or less, it is easier to impregnate the reinforcing fibers with the polyarylene sulfide copolymer (A). It is more preferably 7 mm or less, and even more preferably 5 mm or less.

[0147] The volume content of the fiber-reinforced polyarylene sulfide copolymer composite substrate in the second embodiment of the present invention is preferably 20 to 70 volume %. In other words, the fiber-reinforced polyarylene sulfide copolymer composite substrate preferably contains 20 volume % or more and 70 volume % or less of discontinuous fibers in the entire fiber-reinforced polyarylene sulfide copolymer composite substrate (100 volume %). By containing 20 volume % or more of discontinuous fibers, the strength of a molded product obtained by using the fiber-reinforced polyarylene sulfide copolymer composite substrate can be further improved. 30 volume % or more is more preferable. On the other hand, by containing 70 volume % or less of discontinuous fibers, it is easier to impregnate the discontinuous fibers with the polyarylene sulfide copolymer (A). 60 volume % or less is more preferable, and 50 volume % or less is even more preferable. The volume content can be calculated by the above formula.

[0148] In producing the fiber-reinforced polyarylene sulfide copolymer composite substrate in the second embodiment of the present invention, the substrate can be adjusted to a desired thickness or volume content by heating and pressing using a press. There is no particular restriction on the press as long as it can realize the temperature and pressure required for impregnation of the polyarylene sulfide copolymer (A), and a normal press having a flat platen that moves up and down, or a so-called double belt press having a mechanism for running a pair of endless steel belts can be used.

[0149] The fiber-reinforced polyarylene sulfide copolymer composite substrate in the first and second embodiments of the present invention can be laminated in any configuration, and then molded while applying heat and / or pressure as necessary, to obtain a molded product.

[0150] Examples of methods for applying heat and / or pressure include a press molding method in which a fiber-reinforced polyarylene sulfide copolymer composite substrate laminated in an arbitrary configuration is placed in a mold or on a press plate, and then the mold or press plate is closed to apply pressure, an autoclave molding method in which a molding material laminated in an arbitrary configuration is placed in an autoclave and pressurized and heated, a bagging molding method in which a molding material laminated in an arbitrary configuration is wrapped in a film or the like, and heated in an oven while reducing the internal pressure and applying pressure at atmospheric pressure, a wrapping tape method in which a fiber-reinforced polyarylene sulfide copolymer composite substrate laminated in an arbitrary configuration is wrapped in tape while applying tension, and heated in an oven, and an internal pressure molding method in which a fiber-reinforced polyarylene sulfide copolymer composite substrate laminated in an arbitrary configuration is placed in a mold, and a gas or liquid is injected into a core also placed in the mold to apply pressure, etc. In particular, a molding method in which a press is performed using a mold is preferably used because the molded product obtained has few voids and has excellent appearance quality.

[0151] As the press molding method, a hot press method in which a fiber-reinforced polyarylene sulfide copolymer composite substrate is placed in a mold in advance, pressurized and heated while the mold is closed, and then the mold is cooled while the mold is still closed to cool the fiber-reinforced polyarylene sulfide copolymer composite substrate to obtain a molded product, or stamping molding, which is a method in which a fiber-reinforced polyarylene sulfide copolymer composite substrate is heated in advance to a temperature equal to or higher than the melting temperature of the polyarylene sulfide copolymer (B) using a heating device such as a far-infrared heater, a heating plate, a high-temperature oven, or a dielectric heater, and the polyarylene sulfide copolymer (B) is placed in a melted and softened state on a mold that will become the lower surface of the molding mold, and then the mold is closed to close the mold, and then pressurized and cooled, can be used. There is no particular restriction on the press molding method, but stamping molding is preferable from the viewpoint of accelerating the molding cycle and increasing productivity. The fiber-reinforced polyarylene sulfide copolymer composite substrate and molded article in the first and second embodiments of the present invention can be integrated using an adhesive or an adhesive that has excellent productivity, such as insert molding, outsert molding, or correction treatment by heating, heat welding, vibration welding, or ultrasonic welding, to obtain a composite.

[0152] A composite molded article in which the fiber-reinforced polyarylene sulfide copolymer composite substrate in the first and second embodiments of the present invention and a molded article containing a thermoplastic resin are at least partially bonded to each other is preferred.

[0153] The molded article (substrate for molding and molded article) containing a thermoplastic resin integrated with the fiber-reinforced polyarylene sulfide copolymer composite substrate in the first and second embodiments of the present invention is not particularly limited, and examples thereof include resin materials and molded articles, metal materials and molded articles, inorganic materials and molded articles, etc. Among them, resin materials and molded articles are preferred in terms of adhesive strength with the fiber-reinforced polyarylene sulfide copolymer (B) in the present invention.

[0154] The matrix resin of the molding material and the molded product integrated with the fiber-reinforced polyarylene sulfide copolymer composite substrate in the first and second embodiments of the present invention may be the same type of resin as the fiber-reinforced polyarylene sulfide copolymer composite substrate and the molded product, or may be a different type of resin. In order to further increase the adhesive strength, it is preferable that the resin is the same type. In the case of a different type of resin, it is more preferable to provide a resin layer at the interface.

[0155] The fiber-reinforced polyarylene sulfide copolymer composite substrate obtained by the present invention has excellent heat resistance, chemical resistance, flame retardancy, electrical properties and mechanical properties, and can be used in a variety of applications, including electric and electronic parts, audio device parts, home and office electrical appliance parts, machine-related parts, optical instruments, precision machinery-related parts, plumbing parts, automobile and vehicle-related parts, aerospace-related parts, and others. EXAMPLES

[0156] The method of the present invention will be explained in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.

[0157] [Measurement of glass transition point, melting point, heat of fusion and crystallization temperature] The glass transition point (Tg), melting point (Tm), heat of fusion (ΔHm), and crystallization temperature (Tmc) were measured by differential scanning calorimetry (DSC) using approximately 10-20 mg of amorphous sample prepared by quenching from the molten state. The glass transition point was the inflection point of the baseline shift detected when the temperature was raised from 0°C to 340°C at a rate of 20°C / min. The crystallization temperature was the value of the crystallization peak temperature detected when the temperature was raised from 0°C to 340°C at a rate of 20°C / min, held at 340°C for 1 minute, and cooled to 100°C at a rate of 20°C / min. The melting point was the value of the melting peak temperature detected when the temperature was raised from 0°C to 340°C at a rate of 20°C / min, held at 340°C for 1 minute, cooled to 100°C at a rate of 20°C / min, held at 100°C for 1 minute, and heated again to 340°C at a rate of 20°C / min. The heat of fusion was the amount of heat calculated from the melting peak. The heat of fusion of the polyarylene sulfide copolymer (B) in the fiber-reinforced polyarylene sulfide copolymer composite substrate was calculated by converting the amount of heat calculated from the melting peak into the amount of heat per weight of the polyarylene sulfide copolymer (B) excluding the continuous reinforcing fibers in the fiber-reinforced polyarylene sulfide copolymer composite substrate or the reinforcing fiber substrate in which discontinuous reinforcing fibers are dispersed. Equipment: TA Instruments TA-Q200 Carrier gas: Nitrogen Sample purge flow rate: 50mL / min.

[0158] [Molecular weight measurement] The number average molecular weight Mn and the weight average molecular weight Mw were calculated in terms of polystyrene by gel permeation chromatography (GPC), which is a type of size exclusion chromatography (SEC). When measuring the molecular weight of the polyarylene sulfide copolymer (B) contained in the fiber-reinforced polyarylene sulfide copolymer composite substrate, the fiber-reinforced polyarylene sulfide copolymer composite substrate was immersed in 1-chloronaphthalene at 250°C, shaken for 5 minutes, and then filtered through a membrane filter with a pore size of 1 μm, and the filtrate was collected and analyzed. The measurement conditions for GPC are shown below. Equipment: Senshu Science SSC-7110 Column name: Shodex UT806M x 2 Eluent: 1-chloronaphthalene Detector: Differential refractive index detector Column temperature: 210℃ Pre-thermostat temperature: 250℃ Pump thermostatic chamber temperature: 50℃ Detector temperature: 210℃ Flow rate: 1.0mL / min Sample injection volume: 300 μL.

[0159] [Analysis of Amino Group Amount] The amount of amino groups in the polyarylene sulfide (C) was measured by FT-IR (IR-810 infrared spectrophotometer manufactured by JASCO Corporation) of an amorphous film prepared by quenching from a molten state obtained by heating at 320°C, and the amount of amino groups in the polyarylene sulfide (C) was measured by FT-IR (IR-810 infrared spectrophotometer manufactured by JASCO Corporation) of the 1901 cm -1 The absorption intensity at 3382 cm originating from the amino group -1 The absorption intensity was estimated by comparing the

[0160] [Measurement of weight loss rate upon heating] The weight loss rate of the polyarylene sulfide (C) upon heating was measured using a thermogravimetric analyzer under the following conditions. Equipment: PerkinElmer TGA7 Measurement atmosphere: Nitrogen flow Sample weight: approx. 5 mg Measurement conditions (a) Program temperature 30℃ for 1 minute (b) The program temperature is increased from 30°C to 340°C at a rate of 10°C / min. The weight loss rate was calculated from the weights measured under the above conditions at 320°C and 30°C using the following formula. Weight loss rate (%) = ((weight (mg) at 30°C - weight (mg) at 320°C) / weight (mg) at 30°C) x 100.

[0161] [Evaluation of impregnation state through void observation] The fiber-reinforced polyarylene sulfide copolymer composite substrate was cut, and the thickness direction cross section of the fiber-reinforced polyarylene sulfide copolymer composite substrate was observed as follows. A sample in which the fiber-reinforced polyarylene sulfide copolymer composite substrate was embedded in epoxy resin was prepared, and the sample was polished until the thickness direction cross section of the fiber-reinforced thermoplastic resin filament could be well observed. A digital microscope (Keyence VHX-7000) was photographed at a magnification of 400 times with a CCD microscope. The void ratio of the fiber-reinforced polyarylene sulfide copolymer composite substrate was calculated by measuring the area ratio of the normal part and the void (void part) of the photographed cross section. The void ratio was judged to be 3% or less as ○, more than 3% and 10% or less as △, and more than 10% as ×.

[0162] [Reference example 1] In an autoclave equipped with a stirrer and a bottom plug valve, 10.33 kg (90.0 mol) of 47.9% sodium hydrosulfide, 4.10 kg (99.4 mol) of 97% sodium hydroxide, 20.82 kg (210 mol) of N-methyl-2-pyrrolidone (NMP), and 5.95 kg of ion-exchanged water were charged, and the mixture was gradually heated to 225°C over about 3 hours while passing nitrogen through it at normal pressure, and heating was stopped and cooling was started when 11.44 kg of water and 0.025 kg of NMP were distilled. At this point, the amount of hydrogen sulfide scattered was 2.2 mol, so the amount of inorganic sulfidizing agent in the system after this process was 87.8 mol.

[0163] After that, the mixture was cooled to 200°C, and 13.63 kg (92.7 mol) of p-dichlorobenzene (p-DCB), 1.24 kg (9.78 mol) of 4-aminothiophenol (4-ATP), and 13.88 kg (140 mol) of NMP were added. The reaction vessel was then sealed under nitrogen gas, and the temperature was raised to 260°C at a rate of 0.6°C / min with stirring, and the reaction was carried out at 260°C for 120 minutes.

[0164] After the reaction was completed, the bottom plug valve of the autoclave was immediately opened and the contents were flushed into an apparatus equipped with a stirrer and dried for 1.5 hours in the apparatus equipped with a stirrer at 230° C., and a solid material containing PPS and salts was recovered.

[0165] The collected material and ion-exchanged water were placed in an autoclave equipped with a stirrer, washed at 75°C for 15 minutes, and then filtered three times to obtain a cake. The cake and 30 liters of ion-exchanged water were placed in an autoclave equipped with a stirrer, and the inside of the autoclave was replaced with nitrogen, and then the temperature was raised to 195°C. The autoclave was then cooled, and the contents were filtered through a filter to obtain a cake. The cake obtained was dried at 120°C under a nitrogen stream.

[0166] 3 kg of the obtained dried cake and 30 kg of N-methyl-2-pyrrolidone (NMP) were placed in a container equipped with a stirrer, stirred for 30 minutes, and then filtered to obtain a cake. The obtained cake was washed with 30 L of ion-exchanged water for 15 minutes and filtered three times, and then dried at 120°C for 4 hours under a nitrogen stream to obtain a dried PPS.

[0167] The obtained PPS had an amino group amount of 650 μmol / g, a number average molecular weight of 3,100, a weight average molecular weight of 6,200, a dispersity of 2.0, and a weight loss rate of 2.3% when heated from 30°C to 320°C at a heating rate of 10°C / min.

[0168] [Reference example 2] The PPS obtained in Reference Example 1 and pyromellitic anhydride were placed in a reaction vessel equipped with a stirring blade, and 3,9-bis{2-[3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro[5.5]undecane (ADEKA "ADEKA STAB" AO80) was added as a phenol-based antioxidant to the PPS so that the ratio of the amount of acid anhydride groups in the pyromellitic anhydride to the amount of amino groups in the PPS was 1.2. 0.5 parts by weight per 100 parts by weight of PPS (which can be converted to 0.47 parts by weight per 100 parts by weight of the resulting PPS copolymer), and 0.5 parts by weight of 3,9-bis(2,6-di-t-butyl-4-methylphenoxy)2,4,8,10-tetraoxa-3,9-diphosphapyro[5.5]undecane (ADEKA "Adekastab" PEP36) as a phosphorus-based antioxidant was added per 100 parts by weight of PPS (which can be converted to 0.47 parts by weight per 100 parts by weight of the resulting PPS copolymer). The mixture was heated to 300°C with stirring for 3 minutes, and then heated to 380°C with stirring for 6 minutes, and then cooled to room temperature to obtain a PPS copolymer.

[0169] FT-IR spectrum confirmed that the obtained PPS copolymer contained phenylene sulfide units as structural units and imide groups were introduced. DSC measurement results showed that the glass transition temperature was 114°C, the crystallization temperature was 206°C, the melting point was 263°C, and the heat of fusion was 32 J / g. GPC measurement results showed that Mw was 48,600, Mn was 14,900, and Mw / Mn was 3.3.

[0170] [Reference example 3] The PPS obtained in Reference Example 1 and pyromellitic anhydride were charged into a reaction vessel equipped with a stirring blade so that the ratio of the amount of acid anhydride groups in pyromellitic anhydride to the amount of amino groups in PPS was 1.25. The mixture was heated to 300°C with stirring for 3 minutes, further heated to 380°C with stirring for 3 minutes, and then cooled to room temperature to obtain a PPS copolymer.

[0171] FT-IR spectrum confirmed that the obtained PPS copolymer contained phenylene sulfide units as structural units and imide groups were introduced. DSC measurement showed that the glass transition temperature was 113°C, the crystallization temperature was 172°C, the melting point was 259°C, and the heat of fusion was 21 J / g. GPC measurement showed that Mw was 76,700, Mn was 10,300, and Mw / Mn was 7.5.

[0172] [Example 1] Sixteen bobbins wound with carbon fiber bundles (T700S-12K manufactured by Toray Industries, Inc.) were prepared, and the carbon fiber bundles were continuously fed from each bobbin through a yarn guide. The continuously fed carbon fiber bundles were impregnated with the PPS copolymer of Reference Example 2, which was supplied in a fixed amount from a filled feeder, in the impregnation die. The carbon fibers impregnated with the PPS copolymer of Reference Example 2 in the impregnation die were continuously drawn out from the nozzle of the impregnation die at a drawing speed of 1 m / min using a take-up roll. The temperature when drawing out the carbon fibers was 340°C. The drawn carbon fiber bundles were passed through a cooling roll to cool and solidify the PPS copolymer, and were wound up on a winder. The carbon fiber bundles containing the polyarylene sulfide copolymer were further pressed at 300°C for 30 minutes to obtain a fiber-reinforced PPS copolymer composite substrate having a thickness of 0.2 mm and a volume content of reinforcing fibers of 47%. The evaluation results of the obtained fiber-reinforced PPS copolymer composite substrates are shown in Table 1. In addition, when the fiber-reinforced PPS copolymer composite substrate was immersed in 1-chloronaphthalene at 250°C to measure the molecular weight of the PPS copolymer (B), shaken for 5 minutes, and then filtered through a membrane filter with a pore size of 1 μm, no insoluble resin components were observed.

[0173] [Example 2] The same conditions as in Example 1 were used except that the pressing temperature was changed to 340°C, and a fiber-reinforced PPS copolymer composite substrate with a thickness of 0.2 mm and a volume content of reinforcing fibers of 47% was obtained. The evaluation results of the obtained fiber-reinforced PPS copolymer composite substrate are shown in Table 1. Note that when the fiber-reinforced PPS copolymer composite substrate was immersed in 1-chloronaphthalene at 250°C to measure the molecular weight of PPS copolymer (B), shaken for 5 minutes, and then filtered through a membrane filter with a pore size of 1 μm, no insoluble resin components were observed.

[0174] [Comparative Example 1] The same procedures as in Example 1 were carried out except that the polyarylene sulfide copolymer used was changed to the PPS copolymer of Reference Example 3, 0.1 parts by weight of 3,9-bis{2-[3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro[5.5]undecane (ADEKA "Adeka STAB" AO80) was added as a phenol-based antioxidant relative to 100 parts by weight of the PPS copolymer, and 0.1 parts by weight of 3,9-bis(2,6-di-t-butyl-4-methylphenoxy)2,4,8,10-tetraoxa-3,9-diphosphapyro[5.5]undecane (ADEKA "Adeka STAB" PEP36) was added as a phosphorus-based antioxidant relative to 100 parts by weight of the PPS copolymer, to obtain a fiber-reinforced PPS copolymer composite substrate having a thickness of 0.2 mm and a volume content of reinforcing fibers of 47%. The evaluation results of the obtained fiber-reinforced PPS copolymer composite substrate are shown in Table 1. Note that when the fiber-reinforced PPS copolymer composite substrate was immersed in 1-chloronaphthalene at 250°C to measure the molecular weight of PPS copolymer (B), and then was shaken for 5 minutes and filtered through a membrane filter with a pore size of 1 μm, some insoluble resin components remained on the filter.

[0175] [Comparative Example 2] The same conditions as in Comparative Example 1 were used except that the pressing temperature was changed to 340°C, and a fiber-reinforced PPS copolymer composite substrate with a thickness of 0.2 mm and a volume content of reinforcing fibers of 47% was obtained. The evaluation results of the obtained fiber-reinforced PPS copolymer composite substrate are shown in Table 1. Note that when the fiber-reinforced PPS copolymer composite substrate was immersed in 1-chloronaphthalene at 250°C to measure the molecular weight of PPS copolymer (B), shaken for 5 minutes, and then filtered through a membrane filter with a pore size of 1 μm, some insoluble resin components remained on the filter.

[0176] [Table 1]

[0177] As shown in Examples 1 and 2, in the present invention, a fiber-reinforced polyarylene sulfide copolymer composite substrate can be obtained by impregnating a polyarylene sulfide copolymer having a glass transition point of 95°C or more and 190°C or less, in which the weight-average molecular weight of the polyarylene sulfide copolymer contained in the polyarylene sulfide copolymer composite substrate is 50,000 or more and 100,000 or less, and the crystallization temperature is 165°C or more. In addition, the polydispersity expressed as weight-average molecular weight / number-average molecular weight is small, and the heat of fusion, i.e., the degree of crystallization, is high. It is assumed that the excellent thermal properties and small polydispersity are due to the contribution of the antioxidant. From a comparison of the weight average molecular weight of the polyarylene sulfide copolymer (A) in Reference Example 2 and the weight average molecular weight of the polyarylene sulfide copolymer (B) in Examples 1 and 2, it can be seen that a fiber-reinforced polyarylene sulfide copolymer composite substrate containing a high molecular weight polyarylene sulfide copolymer (B) was obtained by impregnation with a relatively low viscosity polyarylene sulfide copolymer (A) in Examples 1 and 2. By impregnation with a relatively low viscosity polyarylene sulfide copolymer (A), a fiber-reinforced polyarylene sulfide copolymer composite substrate with a good impregnation state was obtained.

[0178] As shown in Comparative Examples 1 and 2, when impregnating with a polyarylene sulfide copolymer (A) having a weight average molecular weight of more than 70,000, a fiber-reinforced polyarylene sulfide copolymer composite substrate containing a higher molecular weight polyarylene sulfide copolymer was obtained, but the impregnation state of the carbon fibers was insufficient due to the high viscosity of the polyarylene sulfide copolymer (A) to be impregnated.

[0179] A comparison of the polyarylene sulfide copolymer (A) of Reference Example 2 with the polyarylene sulfide copolymer (A) of Reference Example 3 shows that heating the polyarylene sulfide (C) and the compound (D) in the presence of an antioxidant makes it possible to obtain a polyarylene sulfide copolymer (A) having a relatively low viscosity, and makes it easier to obtain a fiber-reinforced polyarylene sulfide copolymer composite substrate containing the polyarylene sulfide copolymer (B) having a high crystallization temperature, a small dispersity expressed by weight average molecular weight / number average molecular weight, and a high heat of fusion, i.e., a high degree of crystallization.

[0180] Comparing Examples 1 and 2 with Comparative Examples 1 and 2, it is found that both contain an antioxidant when producing a fiber-reinforced polyarylene sulfide copolymer composite substrate, but Examples 1 and 2, which contain a higher amount of antioxidant, are considered to be better able to suppress crosslinking structures and significant increase in molecular weight due to side reactions, since there is no resin component insoluble in 1-chloronaphthalene at 250°C in the polyarylene sulfide copolymer (B).

Claims

1. A fiber-reinforced polyarylene sulfide copolymer composite substrate obtained by impregnating a reinforcing fiber substrate having continuous reinforcing fibers or discontinuous reinforcing fibers dispersed therein with a polyarylene sulfide copolymer (A) having a glass transition point of 95°C or more and 190°C or less, wherein the polyarylene sulfide copolymer (B) contained in the polyarylene sulfide copolymer composite substrate has a weight average molecular weight of 50,000 or more and 100,000 or less and a crystallization temperature of 165°C or more.

2. The fiber-reinforced polyarylene sulfide copolymer composite substrate according to claim 1 , which contains an antioxidant.

3. 2. The fiber-reinforced polyarylene sulfide copolymer composite substrate according to claim 1, wherein the polyarylene sulfide copolymer (B) contained in the fiber-reinforced polyarylene sulfide copolymer composite substrate has a melting point of 300° C. or lower.

4. The fiber-reinforced polyarylene sulfide copolymer composite substrate according to claim 1, wherein the polyarylene sulfide copolymer (B) contained in the fiber-reinforced polyarylene sulfide copolymer composite substrate has an arylene sulfide unit having a number average molecular weight Mn of 1,000 or more and 10,000 or less.

5. The fiber-reinforced polyarylene sulfide copolymer composite substrate according to claim 4, wherein the arylene sulfide unit of the polyarylene sulfide copolymer (B) contained in the fiber-reinforced polyarylene sulfide copolymer composite substrate and the copolymerization component have a structure linked by an imide group.

6. The fiber-reinforced polyarylene sulfide copolymer composite substrate according to claim 1, wherein the polyarylene sulfide copolymer (B) contained in the fiber-reinforced polyarylene sulfide copolymer composite substrate has at least one structure selected from the following formulas (a) to (s) as a structural unit. 【Chemistry 1】 (R, R 1 , and R 2 is a substituent selected from hydrogen, an alkyl group having 1 to 12 carbon atoms, an arylene group having 6 to 24 carbon atoms, and a halogen group; R, R 1 , and R 2 may be the same or different.)

7. The fiber-reinforced polyarylene sulfide copolymer composite substrate according to claim 1, wherein the polyarylene sulfide copolymer (B) contained in the fiber-reinforced polyarylene sulfide copolymer composite substrate has a dispersity represented by weight average molecular weight / number average molecular weight of 5.0 or less.

8. 2. The fiber-reinforced polyarylene sulfide copolymer composite substrate according to claim 1, wherein the polyarylene sulfide copolymer (B) contained in the fiber-reinforced polyarylene sulfide copolymer composite substrate has a heat of fusion of 15 J / g or more.

9. 2. A method for producing a polyarylene sulfide copolymer composite substrate, comprising impregnating a polyarylene sulfide copolymer (A) having a weight-average molecular weight of 70,000 or less into a reinforcing fiber substrate having continuous reinforcing fibers or a reinforcing fiber substrate having discontinuous reinforcing fibers dispersed therein, characterized in that the ratio of the weight-average molecular weight of the polyarylene sulfide copolymer (B) contained in the obtained polyarylene sulfide copolymer composite substrate to the weight-average molecular weight of the polyarylene sulfide copolymer (A) to be impregnated is more than 1 and 10 or less.

10. The method for producing a fiber-reinforced polyarylene sulfide copolymer composite substrate according to claim 9, wherein the polyarylene sulfide copolymer (A) containing an antioxidant is impregnated into a reinforcing fiber substrate having continuous reinforcing fibers or discontinuous reinforcing fibers dispersed therein.

11. 10. A method for producing a fiber-reinforced polyarylene sulfide copolymer composite substrate according to claim 9, comprising heating a polyarylene sulfide (C) containing amino groups in the range of 400 μmol / g or more and 5,000 μmol / g or less and having a weight loss rate of 5 wt% or less when heated from 30 ° C. to 320 ° C. at a heating rate of 10 ° C. / min, and at least one compound (D) selected from the following formulas (a') to (u') to obtain a polyarylene sulfide copolymer (A), and impregnating the polyarylene sulfide copolymer into a reinforcing fiber substrate having continuous reinforcing fibers or discontinuous reinforcing fibers dispersed therein. 【Chemistry 2】 (X is two carboxyl groups bonded to two adjacent carbon atoms, or an acid anhydride group derived from the two carboxyl groups; R, R 1 , and R 2 is a substituent selected from hydrogen, an alkyl group having 1 to 12 carbon atoms, an arylene group having 6 to 24 carbon atoms, and a halogen group; R, R 1 , and R 2 may be the same or different. In addition, the aromatic ring of each compound may be di- or tri-substituted, and the multiple substituents X substituted on one aromatic ring may be the same or different.

12. The method for producing a fiber-reinforced polyarylene sulfide copolymer composite substrate according to claim 11, wherein the heating is carried out in the presence of an antioxidant.

13. 12. The method for producing a fiber-reinforced polyarylene sulfide copolymer composite substrate according to claim 11, wherein the ratio of the total amount of carboxyl groups and acid anhydride groups contained in the compound (D) to the total amount of amino groups contained in the polyarylene sulfide (C) exceeds 1.02 when the polyarylene sulfide (C) and the compound (D) are heated.

14. The method for producing a fiber-reinforced polyarylene sulfide copolymer composite substrate according to claim 11, wherein the heating is carried out substantially in the absence of a solvent.

15. The fiber-reinforced polyarylene sulfide copolymer composite substrate according to claim 1, wherein the reinforcing fibers include carbon fibers and contain 20 to 70 volume % of the reinforcing fibers.

Citation Information

Patent Citations

  • Crystalline polyimide containing cumulative phenylenesulfideunit

    JP1987084124A

  • Polyarylenesulfide block copolymer, manufacture and use

    JP1989045433A

  • Continuous fiber reinforced polyarylene sulfide

    JP2015519423A

  • Polyarylene sulfide copolymer and method for producing same

    WO2019151288A1

  • Fiber-reinforced polyarylene sulfide copolymer composite substrate, method for manufacturing same, and molded article including same

    WO2021020334A1